Insulative adhesive tape
Patent Information
- Application Number
- JP2022169626
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-05-13
- Filing Date
- 2022-10-24
- Publication Date
- 2025-02-05
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing insulating adhesive tapes used in electric vehicles and fuel cell vehicles suffer from reverse tracking phenomena, insufficient insulation properties, and lack of heat resistance, especially at higher voltages, and are difficult to wrap around miniaturized components.
An insulating adhesive tape composed of a laminate structure with an insulating layer, a glass cloth layer, and an adhesive layer, where at least one of the layers is impregnated into the glass cloth layer, providing improved tracking resistance, insulation properties, and winding processability.
The laminate structure enhances the tape's heat resistance, insulation properties, and winding processability, preventing reverse tracking and ensuring effective adhesion to miniaturized components.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical field
[0001] The present disclosure particularly relates to an insulating adhesive tape that has heat resistance and good tracking resistance that does not cause a reverse trend phenomenon, has high insulation properties, and has excellent winding processability. [Background technology]
[0002] In recent years, around the world, EVs (electric vehicles) and HEVs (hybrid electric vehicles), which run by driving a motor with battery electricity, and FCVs (which run by driving a motor by electricity obtained from the chemical reaction of hydrogen and oxygen) have become popular worldwide. fuel cell vehicles) etc. are rapidly becoming popular. Currently, the voltage of the battery used to drive the motor is 400V, but it is expected to increase to 800V and even 1000V to make cables thinner and to shorten charging time, and it has heat resistance and high tracking resistance. Insulating adhesive tape is in demand. In addition, due to the trend toward lighter weight and higher density, components are becoming smaller and the curved surface (R) of the part around which the tape is wrapped is becoming smaller, so there is a demand for insulating adhesive tapes that are thin, flexible, and hard to peel off. Wrapping workability and abbreviation below). In addition, although the CTI is certified as 600 volts, there is a problem with the reverse trend phenomenon in which tracking occurs in the low voltage band around 300 volts. [Prior art documents] [Patent document]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 2010-76261 [Summary of the invention] [Problem to be solved by the invention]
[0004] In the insulating adhesive tape disclosed in Prior Document 1, a reverse trend phenomenon occurred and the heat resistance was greatly lacking. In addition, the insulation properties were insufficient, as dielectric breakdown occurred at low voltages in dielectric breakdown voltage tests.
[0005] The present disclosure has been made in view of the above, and aims to provide heat resistance and good tracking resistance that does not cause the reverse trend phenomenon, high insulation properties, and winding processability. Our objective is to provide a good insulating adhesive tape. [Means to solve the problem]
[0006] In order to achieve the above object, an insulating adhesive tape is provided which is composed of a laminate of three or more layers having at least an insulating layer, an adhesive layer, and a glass cloth layer therebetween, the insulating adhesive tape comprising an insulating layer, a glass cloth layer, and an adhesive layer. It has a laminated structure. Specifically, the details are as follows.
[0007] That is, the present invention provides an insulating adhesive tape having an insulating layer, an adhesive layer, and a glass cloth layer, wherein the glass cloth layer is located between the insulating layer and the adhesive layer, and the glass cloth layer is located between the insulating layer and the adhesive layer. relates to an insulating adhesive tape characterized in that at least one of the insulating layer or the adhesive layer is impregnated.
Effect of the invention
[0008] According to the present disclosure, there is provided an insulating adhesive tape that has excellent tracking resistance, good winding processability even for miniaturized high-voltage components, and also has high insulation properties and heat resistance. be able to. [Brief explanation of drawings]
[0009]
Figure 1
Figure 2
[0010] Hereinafter, this embodiment will be described in detail based on the drawings. The following description of preferred embodiments is merely illustrative in nature and is not intended to limit the invention, its applications, or its uses. In the present invention, insulating adhesive tape, adhesive sheet, adhesive tape, and adhesive film are synonymous terms.
[0011] [Insulating adhesive tape] The insulating adhesive tape according to Embodiment 1 will be explained using FIG. 1. FIG. 1(1) is a plan view of the insulating adhesive tape 1, and a glass cloth layer is shown for convenience. FIG. 1(2) is a cross-sectional view of the tape at the position D-D' in FIG. 1(1). As shown in FIG. 1(2), the insulating adhesive tape 1 has an insulating layer 12, a glass cloth layer 11, and an adhesive layer 13, and the glass cloth layer is located between the insulating layer and the adhesive layer (hereinafter referred to as (also abbreviated as tape). The insulating layer 12 and the adhesive layer 13 are impregnated into the glass cloth layer 11 and are in contact with each other in the glass cloth layer. It is sufficient that at least one of the insulating layer 12 and the adhesive layer 13 is impregnated into the glass cloth layer 11, but it is preferable that both the insulating layer 12 and the adhesive layer 13 are impregnated from the viewpoint of improving heat resistance. . Each impregnated portion of the insulating layer 12 and adhesive layer 13 in the insulating adhesive tape 1 will be explained in detail. A dotted line L1 in FIG. 1(2) is the outermost layer boundary line of the insulating layer 12. L3 is the interface where the insulating layer and the adhesive layer touch. L5 is the outermost layer boundary line of the adhesive layer 13. Here, the distance between L1 and L3 is defined as the thickness of the insulating layer 12, the distance between L3 and L5 is defined as the thickness of the adhesive layer, and the distance between L1 and L5 is defined as the thickness of the tape. Furthermore, L2 and L4 indicate the apexes of the convex portions on the upper and lower surfaces, respectively, when the glass cloth layer is observed from a cross section, and in this application, the distance between L2 and L4 is defined as the thickness of the glass cloth layer. Further, L1 to L2 in which the glass cloth layer is not impregnated with the insulating layer 12 are defined as an insulating non-impregnated layer 12a, and L2 to L3 in which the insulating layer 12 is impregnated are defined as an insulating impregnated layer 12b. Similarly, L4 to L5 in which the glass cloth layer is not impregnated with the adhesive layer 13 is defined as an adhesive non-impregnated layer 13a, and L3 to L4 in which the adhesive layer 13 is impregnated is defined as an adhesive impregnated layer 13b.
[0012] FIG. 2 is a schematic tape cross-sectional view illustrating a form in which a part of the glass cloth layer has a void. In this case, as shown in FIG. 2, an insulating impregnated layer is formed between the insulating layer interfaces L3-1 and L2 on the glass cloth layer impregnated side. Similarly, the area between the adhesive layer interfaces L3-2 and L4 on the glass cloth layer impregnated side becomes the adhesive layer impregnated layer. Although there may be voids in a part of the glass cloth layer, from the viewpoint of improving insulation properties, it is best to have the insulating layer 12 and adhesive layer 13 completely impregnated into the glass cloth layer 11 and have no voids, as shown in Figure 1. preferable.
[0013] The thickness of the insulating adhesive tape is preferably 30 to 200 μm, more preferably 45 to 100 μm. When the thickness is 30 μm or more, heat resistance and insulation properties are improved, and when it is 200 μm or less, winding processability is improved.
[0014] The thickness of the glass cloth layer 11 is preferably 10 μm to 50 μm, more preferably 20 μm to 35 μm. By being within a preferable range, the insulating adhesive tape has sufficient strength while being highly flexible, and has improved heat resistance and winding processability. The thickness of the insulating layer 12 is preferably 1 μm to 100 μm, more preferably 20 μm to 60 μm. The thickness of the insulating non-impregnated layer 12a is preferably 1 to 30 μm, more preferably 5 to 15 μm. When the thicknesses of the insulating layer 12 and the insulating non-impregnated layer 12a are within the above preferred ranges, the tracking resistance and winding processability of the tape are improved in a well-balanced manner. The ratio of the thickness of the insulating impregnated layer 12b to the thickness of the glass cloth layer is preferably 50% or more, more preferably 70% or more. When it is within a preferable range, the gaps in the glass cloth layer 11 are filled with the insulating layer, so that the insulation and heat resistance are greatly improved.
[0015] The thickness of the adhesive layer 13 is preferably 5 μm to 100 μm, more preferably 20 μm to 40 μm. The thickness of the adhesive non-impregnated layer 13a is preferably 5 μm to 50 μm, more preferably 20 μm to 35 μm. By having the thickness of the adhesive layer 13 and the adhesive non-impregnated layer 13a within the above-mentioned preferred range, sufficient adhesive performance can be obtained against various irregularities of adherends.
[0016] The ratio of the thickness of the adhesive impregnated layer 13b to the thickness of the glass cloth layer is preferably from 1 to less than 50%, more preferably from 1 to less than 30%. When the content is within the above range, the gaps in the glass cloth layer 11 are filled with a large amount of the insulating layer, improving the insulation properties of the tape, and when the content is 1% or more, the adhesion with the glass cloth layer is improved. As mentioned above, it is preferable that the glass cloth layer 11 has no voids and is filled with the insulating impregnated layer 12b or the adhesive impregnated layer 13b, and the sum of the thicknesses of the insulating impregnated layer 12a and the adhesive impregnated layer 13b is the glass cloth layer. A thickness of 11 is preferable from the viewpoint of improving insulation properties.
[0017] The thickness of each layer of the insulating adhesive tape was evaluated by scanning electron microscopy (SEM observation) of the cross section of the tape, and was the average value measured at 10 arbitrary points in the observed image at a magnification of 300 to 1000 times. The cross section to be measured is one that has a crease and a place where the warp and weft intersect, as shown at E-E' in Figure 3(1). This is because the thicknesses of the insulating layer 12 and the adhesive layer 13 can be easily measured because the locations where the warp and weft shown in FIG. 3(2) are not present can be confirmed. The method for distinguishing each layer when measuring the thickness is as shown in Figure 3 (2), based on the thickness of the insulating adhesive tape 1, from the outermost surface of each of the insulating non-impregnated layer 12a and the adhesive non-impregnated layer 13a, The thickness of the insulating non-impregnated layer 12a and the adhesive non-impregnated layer 13a is measured to be the smallest among the positions that can be confirmed, and the thickness of the glass cloth layer 11 is determined by subtracting the thickness from the entire thickness of the tape. In other words, the glass cloth layer 11 is measured to have the largest thickness including its unevenness, and the thickness subtracted from the overall thickness of the tape is the thickness of the insulating non-impregnated layer 12a and the adhesive non-impregnated layer 13a.
[0018] Methods for obtaining the cross section of the insulating adhesive tape 1 include breaking the target sample frozen with liquid nitrogen, etc. (freeze-fracture method), cutting the target sample with a sharp knife such as a razor (microtome method), or cutting it out with a cutter, etc. There are various methods that can be used to obtain a smooth cross section, such as smoothing the cross section of the target sample using abrasive paper, or irradiating the sample with an ion beam using a cross section polisher (ion milling method). However, among these methods, the ion milling method is preferred. In addition, if it is difficult to judge by color or shape, the cross section may be examined using a scanning probe microscope (sometimes referred to as SPM), as there is a large difference in elastic modulus between the glass cloth layer 11, insulating layer 12, and adhesive layer 13. It is also possible to distinguish each layer from an image expressing the magnitude of the elastic modulus. Furthermore, if the interface between the insulating impregnated layer 12b and the adhesive impregnated layer 13b within the glass cloth layer 11 cannot be sufficiently determined, the ethyl acetate is stirred while the adhesive tape is immersed in a container filled with ethyl acetate at 80°C for 12 hours. After eluting and removing only the adhesive layer by fluidizing the glass cloth with a dipping device, the layer remaining on the glass cloth layer can be determined to be the insulating impregnated layer 12b by cross-sectional observation, and this can be determined in combination with the thickness measurement before dipping.
[0019] The 180°C peel adhesion of the adhesive layer of the insulating adhesive tape to the stainless steel plate is preferably 0.1 to 100 kgf / 20 mm. Considering the prevention of unintentional peeling and the method of wrapping it around a tubular core material and pulling out only the necessary amount for use, from a practical standpoint, 1 to 50 kgf / 25 mm is more preferable, and 5 to 30 kgf / 25 mm is even more preferable. The adhesive force measurement of the product of the present invention refers to the value measured using a "cold rolled stainless steel plate" described in JIS G 4305:2012 in accordance with JIS Z0237:2009.
[0020] [Glass cloth layer] As shown in FIG. 1, the glass cloth layer 11 is a layer located between the insulating layer and the adhesive layer and supporting the insulating adhesive tape. The glass cloth layer 11 has a layer partially impregnated with at least one of the insulating layer 12 or the adhesive layer 13, that is, it has at least the insulating impregnated layer 12b or the adhesive impregnated layer 12b as shown in FIG. 1(2). Glass cloth is made by weaving glass threads, and glass threads are made from smaller diameter glass filaments bound together with an adhesive (also called yarn). By including such a glass cloth layer 11, heat resistance and winding workability are greatly improved.
[0021] The glass thread preferably has a diameter of 100 to 500 μm, more preferably 125 to 400 μm, and even more preferably 150 to 250 μm. Within the above range, heat resistance and winding processability are improved. The diameter of the glass threads is the average value of 20 warp threads and 20 weft threads when observed with a microscope at a magnification of 50 to 100 perpendicular to the surface of the glass cloth layer 11 or the insulating adhesive tape. The cross section of the glass thread is not a perfect circle, but most of it is an extreme ellipse, and the diameter of the observed glass thread matches the longest diameter of the ellipse. In other words, C in Figure 1 corresponds to the diameter of the glass thread. If visual confirmation is difficult, use the average value of the longest diameters of 20 randomly selected tapes by observing the cross section of the tape. By setting it within a preferable range, it is possible to sufficiently satisfy the strength required for a flexible and insulating adhesive tape.
[0022] The glass thread is preferably formed by bundling 10 to 500 glass filaments, more preferably 30 to 120, and more preferably 40 to 80. The diameter of the glass filament is 1 to 10 μm, more preferably 3.5 μm to 5.5 μm. The smaller the diameter of the glass filament or the fewer the number of filaments that are bundled, the lower the strength of the glass thread, but the more flexible it becomes, and by setting it within a preferable range, it is possible to achieve sufficient flexibility and the strength required for an insulating adhesive tape. can be satisfied. Tapes with low flexibility tend to have the problem that the ends of the tape tend to peel off during the winding process.
[0023] Since glass cloth is a woven fabric, its weaving method is not limited, but is selected from plain weave, twill weave, and satin weave, with plain weave being preferred from the viewpoint of productivity and uniformity. Weave density is the average number of threads in the warp direction or threads in the weft direction in a 10 mm length range at three arbitrary points observed under a microscope at 100 to 500 times the surface of the glass cloth, and is 10 ~50 lines / 10mm, more preferably 15-40 lines / 10mm, even more preferably 20-35 lines / 10mm. The observation range of 10 mm is set perpendicular to the direction of the glass thread being observed. The weaving density of the glass cloth layer of the insulating adhesive tape can be confirmed by microscopic observation of the surface of the tape when the insulating layer or the adhesive layer is transparent. If it cannot be confirmed, it can be confirmed by dissolving and removing the adhesive layer with an organic solvent. When the number of glass threads increases, the strength of the glass cloth layer increases, but the impregnability of the insulating layer and adhesive layer decreases, and many voids are likely to occur due to insufficient impregnation. becomes worse. When the number of glass threads is small, the impregnation of the insulating layer and adhesive layer into the glass cloth increases, reducing voids and increasing insulation, but the tensile strength decreases, causing problems such as the tape tearing during processing. It becomes easier. By falling within a preferable range, it is possible to provide an edge adhesive tape with high insulation properties and excellent winding processability. If a glass non-woven fabric or glass fiber filler is used instead of glass cloth between the insulating layer and the adhesive layer, the glass non-woven fabric will be difficult to impregnate with resin and the insulation will be significantly inferior, but if a glass fiber filler is used cannot be used because its heat resistance is greatly inferior.
[0024] The composition of the glass used for glass cloth is not particularly limited, but for example, by adjusting the composition ratio of silicon oxide, aluminum oxide, magnesium oxide, and boron oxide, it is possible to improve not only the strength but also the melting point and dielectric constant. , density can be changed and performance can be imparted to the present invention. For example, when the ratio of silicon oxide to aluminum oxide is increased, the tensile strength at break increases, and when the ratio of boron oxide is increased, the density and dielectric constant decrease.
[0025] The glass filament diameter and the number of focused glass filaments can be confirmed by various methods and are not particularly limited, but can be confirmed, for example, by microscopically observing a cross section of the tape structure of the present invention. Methods of obtaining a cross section include splitting the target sample frozen with liquid nitrogen, etc. (freeze-fracture method), cutting the target sample with a sharp blade such as a razor (microtome method), or cutting the target sample with a cutter, etc. cross-section polishing to smooth the surface with abrasive paper. There is a method (ion milling method) in which a sample is processed by irradiating an ion beam with a shear device, and a smooth cross section can be obtained by various methods, but among these, the ion milling method is preferable. The diameter is measured by taking the average value of the long and short sides of the cross-sections of ten glass filaments of any observed warp and weft. In addition, the number of warp and weft yarns is determined from three arbitrary points on a 10 mm square. If the number of warp yarns and weft yarns cannot be visually recognized, after impregnating the tape with an organic solvent, the dissolved adhesive layer is removed, and the surface of the exposed glass cloth layer is It can also be confirmed by microscopic observation. Further, if the glass cloth layer is sufficiently visible from the tape surface, immersion in an organic solvent is not necessary. In addition, if it is difficult to judge based on color or shape, since there is a large difference in elastic modulus between glass and resin, a cross section can be imaged using a scanning probe microscope (sometimes referred to as SPM) to determine the magnitude of the elastic modulus. You can also check the rendered image.
[0026] As the glass cloth, commercially available products can be used. For example, E-1037 (thickness: 27 μm) manufactured by Nitto Boseki Co., Ltd. can be mentioned. Alternatively, those produced by conventionally known methods may be used.
[0027] [Insulating layer] The insulating layer is a cured product of an insulating composition. The insulating layer 12 is located above the adhesive layer 13 of the insulating adhesive tape 1 in FIG. 1(2), and is subdivided into an insulating non-impregnated layer 12a that is not impregnated with the glass cloth layer 11 and an insulating impregnated layer 12b that is impregnated with the glass cloth layer 11. Note that when the adhesive layer 13 impregnates the entire glass cloth layer, the insulating impregnated layer 12b may not be present. The insulating layer 12 provides the insulating adhesive tape with tracking resistance, insulation, and flexibility, that is, with winding processability. The mechanism by which tracking occurs is that when a voltage is applied to an insulating layer with contamination, dust, etc. and moisture present, a current flows through the insulating layer, and when the moisture evaporates and dries due to Joule heat, the current decreases. It is said that this is caused by concentration of the insulating layer in a certain area, causing a micro discharge, which causes part of the insulating layer to decompose and carbonize.
[0028] Therefore, the material constituting the insulating layer 12 should (1) contain a small amount of carbon (difficult to form a carbonized conductive path), (2) have high insulation properties, (3) have high heat resistance, and (4) be flexible. Ideally, the insulating composition, which is a precursor thereof, should be applied to the glass cloth in order to suppress voids in the insulating impregnated layer 12b and the glass cloth layer 11 after curing. Ideally, the glass cloth layer 11 should have properties that allow easy impregnation and prevent the formation of voids within the glass cloth layer 11. In particular, for reason (1), simply improving insulation does not solve the tracking phenomenon.
[0029] Examples of materials having both the above properties (1) to (4) include products cured by active energy rays, polyimides with an aromatic ring concentration of 30% by mass or less, and polyamides with an aromatic ring concentration of 30% by mass or less. Preferably, the resin is the main component. From the viewpoint of further improving the winding processability, a cured product using active energy rays is more preferable.
[0030] <Cured product by active energy rays> Products cured by active energy rays contain polymerizable compounds, and when irradiated with active energy rays such as ultraviolet rays or electron beams, the compounds polymerize and harden. Generally, ethylenic double bonds ( Refers to those having an alkenyl group). Acrylic materials mainly having an acrylic acid ester skeleton or a methacrylic acid ester skeleton are preferable because they are available as ready-made products and are relatively inexpensive.In particular, urethane acrylate oligomers (simply referred to as oligomers) are preferred because they are easy to adjust flexibility and material strength. ) is preferable.
[0031] The insulating composition for forming the insulating layer 12 is mainly composed of components that can be cured by active energy rays, and contains a crosslinking agent and additives in order to easily impregnate the glass cloth and prevent voids from forming during curing. It is preferable to add agents and solvents and use it as a coating liquid.
[0032] As the active energy ray, electromagnetic waves or charged particle beams having energy quantum can be used, and specifically, ultraviolet rays, electron beams, etc. can be used. In particular, ultraviolet light is preferred because it is easy to handle. Irradiation with ultraviolet light can be performed using a high-pressure mercury lamp, a xenon lamp, or the like. The irradiation intensity of ultraviolet rays is preferably about 50 to 1000 mW / cm2. Further, the cumulative amount of ultraviolet light is preferably 50 to 10,000 mJ / cm2, more preferably 80 to 5,000 mJ / cm2, and even more preferably 200 to 2,000 mJ / cm2. On the other hand, electron beam irradiation can be performed using an electron beam accelerator or the like. The amount of electron beam irradiation is preferably about 10 to 1000 krad.
[0033] The urethane acrylate oligomer is a reaction product with at least a polyvalent isocyanate and a (meth)acrylate having an active hydrogen group, and is characterized by having a plurality of alkenyl groups at the end of the molecule. Extensions with polyol compounds, acids, and amine compounds are also common. Urethane acrylate oligomers, which have multiple alkenyl groups in their molecules, are rapidly cured by active energy such as ultraviolet rays or electron beams due to the unsaturated carbon bonds derived from the acrylate. The obtained cured product is rigid and has excellent chemical resistance. When a radically polymerizable crosslinking component is crosslinked by ultraviolet rays or the like, a photopolymerization initiator can be used, and a polymerization accelerator can also be used in combination. In the case of crosslinking by electron beam, these may not be added.
[0034] The weight average molecular weight (Mw) of the urethane acrylate oligomer is preferably 300 to 15,000, more preferably 500 to 5,000, and even more preferably 700 to 2,500. By being less than 15,000, it has excellent impregnating properties to the glass cloth when drying (uncured and solvent-free state) after coating on the glass cloth, and has excellent bubble removal during drying, and eliminates voids inside the glass cloth. The occurrence of this can be suppressed and the insulation properties can be improved. If it is 300 or more, shrinkage during curing can be suppressed, and the resulting cured product is less likely to become brittle, ensuring flexibility and improving winding workability.
[0035] The number of functional groups in the urethane acrylate oligomer is preferably 2 to 5, more preferably 3 to 4. For example, when 100 parts of a trifunctional urethane acrylate oligomer is mixed with 100 parts of a pentafunctional urethane acrylate oligomer, it can be considered as substantially tetrafunctional. By being within a preferable range, it is possible to suppress waviness and voids due to curing shrinkage of the insulating layer, and the insulating properties are improved due to the high crosslinking density while maintaining flexibility. By being within a more preferable range, flexibility, strength, and insulation properties are well balanced.
[0036] Urethane acrylate oligomers contain polyoxyalkylene chains (also called EO chains: ethylene oxide chains, PO chains: propylene oxide chains, ethylene glycol chains, propylene glycol chains) from the viewpoint of shrinkage control and flexibility after curing. It is preferable to have. Polyoxyalkylene chains can be easily identified by infrared absorption spectrum (IR spectrum), and even if polyoxyalkylene chain-containing additives are included as additives, they can be immersed in MEK (methyl ethyl ketone) solution at 25°C for 3 days. If the infrared absorption spectrum after drying is sufficiently distinguishable, it can be determined that the cured product is a urethane acrylate oligomer that is incorporated into the structure of the urethane acrylate oligomer, that is, has a polyoxyalkylene chain. If the infrared absorption spectrum shifts due to steric hindrance, NMR spectroscopy and gas mask chromatography may be used in combination. When using gas chromatography, the presence or absence can be determined by using the column passage time of the EO chain and PO chain as a calibration curve.
[0037] 2-Hydroxyethyl acrylate and 2-hydroxyacrylate are monofunctional hydroxyacrylates. Droxypropyl acrylate, 2-hydroxy-3-chloropropyl acrylate, N-(2-hydroxyethyl)acrylamide, 2-hydroxy-3-phenoxypropyl acrylate, 2-hydroxy-3-allyloxypropyl acrylate, acrylic acid-2 -Hydroxy-3-allyloxypropyl, 2-acryloyloxyethyl-2-hydroxypropyl phthalate can be used.
[0038] Monofunctional hydroxy-containing methacrylates such as 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxy-3-chloropropyl methacrylate, 2-hydroxy-3-phenoxypropyl methacrylate, 2-hydroxy-3-allyloxypropyl methacrylate, 2 -methacryloyloxyethyl-2-hydroxypropyl phthalate can be used.
[0039] Difunctional acrylates include 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol 200 diacrylate, Polyethylene glycol 300 diacrylate, polyethylene glycol 400 diacrylate, polyethylene glycol 600 diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, tetrapropylene glycol diacrylate, polypropylene glycol 400 diacrylate, polypropylene glycol 700 diacrylate, neopentyl Glycol diacrylate, neopentyl glycol PO modified diacrylate, hydroxypivalic acid neopentyl glycol ester diacrylate, caprolactone adduct diacrylate of hydroxypivalic acid neopentyl glycol ester, 1,6-hexanediol bis(2-hydroxy-3- Acryloyloxypropyl) ether, Bis(4-acryloxypolyethoxyphenyl)propane, 1,9-nonanediol diacrylate, Pentaerythritol diacrylate, Pentaerythritol diacrylate monostearate, Pentaerythritol diacrylate monobenzoate, Bisphenol A diacrylate Acrylate, EO modified bisphenol A diacrylate, PO modified bisphenol A diacrylate, hydrogenated bisphenol A diacrylate, EO modified hydrogenated bisphenol A diacrylate, PO modified hydrogenated bisphenol A diacrylate, bisphenol F diacrylate, EO modified bisphenol F Diacrylate, PO-modified bisphenol F diacrylate, EO-modified tetrabromobisphenol A diacrylate, tricyclodecane dimethylol diacrylate, isocyanuric acid EO-modified diacrylate, ethoxylated isocyanuric acid diacrylate, 2-hydroxy-1,3-dia Chryloxypropane and pentaerythritol diacrylate can be used.
[0040] Trifunctional acrylates include glycerin PO modified triacrylate, trimethylolpropane triacrylate, trimethylolpropane EO modified triacrylate, trimethylolpropane PO modified triacrylate, isocyanuric acid EO modified triacrylate, ethoxylated isocyanuric acid triacrylate, isocyanuric acid EO Modified ε-caprolactone modified triacrylate, 1,3,5-triacryloylhexahydro-s-triazine, pentaerythritol triacrylate, dipentaerythritol triacrylate tripropionate can be used. From the viewpoint of flexibility, isocyanuric acid EO-modified triacrylate, ethoxylated isocyanuric acid triacrylate, and isocyanuric acid EO-modified ε-caprolactone-modified triacrylate are preferred.
[0041] As tetrafunctional or higher functional acrylates, pentaerythritol tetraacrylate, acrylate made by linking two molecules of ethoxylated isocyanuric acid diacrylate with hexamethylene diisocyanate, dipentaerythritol tetraacrylate, dipentaerythritol pentaacrylate monopropionate, dipentaerythritol hexaacrylate , Ji Pentaerythritol ε-caprolactone-modified hexaacrylate, dipentaerythritol EO-modified hexaacrylate, tetramethylolmethanetetraacrylate, oligoester tetraacrylate, pentaerythritol tetraacrylate, and tris(acryloyloxy)phosphate can be used. From the viewpoint of flexibility, dipentaerythritol EO-modified hexaacrylate is preferred.
[0042] Difunctional methacrylates include 1,4-butanediol dimethacrylate, 1,6-hexanediol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, polyethylene glycol 200 dimethacrylate, Polyethylene glycol 300 dimethacrylate, polyethylene glycol 400 dimethacrylate, polyethylene glycol #600 dimethacrylate, dipropylene glycol dimethacrylate, tripropylene glycol dimethacrylate, tetrapropylene glycol dimethacrylate, polypropylene glycol 400 dimethacrylate, polypropylene glycol 700 dimethacrylate, Neo Pentyl glycol dimethacrylate, neopentyl glycol PO modified dimethacrylate, hydroxypivalic acid neopentyl glycol ester dimethacrylate, caprolactone adduct dimethacrylate of hydroxypivalic acid neopentyl glycol ester, 1,6-hexanediol bis(2-hydroxy-3 -methacryloyloxypropyl) ether, 1,9-nonanediol dimethacrylate, pentaerythritol dimethacrylate, pentaerythritol dimethacrylate monostearate, pentaerythritol dimethacrylate monobenzoate, 2,2-bis(4-methacryloxypolyethoxyphenyl) Propane, bisphenol A dimethacrylate, E O modified bisphenol A dimethacrylate, PO modified bisphenol A dimethacrylate, hydrogenated bisphenol A dimethacrylate, EO modified hydrogenated bisphenol A dimethacrylate, PO modified hydrogenated bisphenol A dimethacrylate, bisphenol F dimethacrylate , EO modified bisphenol F dimethacrylate, PO modified bisphenol F dimethacrylate, EO modified tetrabromobisphenol A dimethacrylate, tricyclodecane dimethylol dimethacrylate, isocyanuric acid EO modified dimethacrylate, 2-hydroxy-1,3-dimethacryloxy Propane, tricyclodecane dimethanol diacrylate can be used. .
[0043] Trifunctional methacrylates include glycerin PO modified trimethacrylate, trimethylolethane trimethacrylate, trimethylolpropane trimethacrylate, trimethylolpropane EO modified trimethacrylate, trimethylolpropane PO modified trimethacrylate, isocyanuric acid EO modified trimethacrylate, isocyanuric acid EO modified trimethacrylate ε-caprolactone modified trimethacrylate, 1,3,5-trimethacryloylhexahydro-s-triazine, pentaerythritol trimethacrylate, dipentaerythritol trimethacrylate tripropionate can be used. From the viewpoint of flexibility, isocyanuric acid EO modified trimethacrylate and isocyanuric acid EO modified ε-caprolactone modified trimethacrylate are preferred.
[0044] As tetrafunctional or higher functional methacrylates, pentaerythritol tetramethacrylate, dipentaerythritol pentamethacrylate monopropionate, dipentaerythritol hexamethacrylate, dipentaerythritol ε-caprolactone modified hexamethacrylate, dipentaerythritol EO modified hexamethacrylate, tetramethylolmethanetetra Methacrylate, oligoester tetramethacrylate, tris(methacryloyloxy)phosphate, and compounds obtained by modifying these with ε-lactone can be used. From the viewpoint of flexibility, dipentaerythritol EO-modified hexamethacrylate is preferred.
[0045] Diamines include ethylenediamine, 1,3-propanediamine, 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9- Diamines with linear aliphatic structures such as nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, 1,14-tetradecanediamine, 1,16-hexadecanediamine; propylene diamine , 1,2-butanediamine, 1,3-butanediamine, 2,3-butanediamine, 2-methyl-1,3-propanediamine, neopentyldiamine, 1,2-pentanediamine, 3-methyl-1, Diamines with a branched aliphatic structure such as 5-pentanediamine and 1,8-nonanediamine; diamines with an alicyclic structure such as cyclopropanediamine, cyclohexanediamine, cyclohexanediamine, tricyclodecanediamine, adamantyldiamine, etc. Can be used.
[0046] The protective agent preferably contains a photopolymerization initiator to promote photopolymerization of the urethane acrylate oligomer. Specific examples of the photopolymerization initiator include the following. Diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzylmethyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl Phenylketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butane, oligo{2- Hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone}, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2 - Acetophenones such as methylpropan-1-one; Benzoins such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether; 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis( Examples include, but are not limited to, phosphines such as 2,4,6-trimethylbenzoyl)-phenylphosphine oxide; and phenylglyoxylic methyl ester. More specifically, IrgaCure 651, IrgaCure 184, Darocure 1173, IrgaCure 500, IrgaCure 1000, IrgaCure 2959, IrgaCure 907, IrgaCure 369, IrgaCure 379, IrgaCure 1700, IrgaCure 149, IrgaCure Cure 1800, Irgacure 1850, Irgacure 819, Irgacure 784, Irgacure 261, Irgacure OXE-01 (CGI124), CGI242 (BASF), ADEKA Optomer N1414, ADEKA OPTOMER N1717 (ADEKA), EsACure1001M( LAmBerti), diazonium compound publication, organic azide compounds, ortho-quinone diazides, various onium compounds including iodonium compounds, metal allene complexes, transition metal complexes containing transition metals such as ruthenium, aluminate complexes, 2,4 ,5-triarylimidazole dimer, carbon tetrabromide, organic halogen compounds, sulfonium complexes or oxosulfonium complexes, aminoketone oxime ester compounds, and the like.
[0047] Further, as a photopolymerization initiator, it is possible to use a hydrogen abstraction type radical initiator, and specific examples include aromatic ketones such as acetophenone, benzophenone, benzyl, Michler's ketone, thioxanthone, or anthraquinone. , but not limited to. It is common in the art for these compounds to be used in combination with tertiary amines, specifically trimethylamine, triethylamine, tripropylamine, tributylamine, N-methyldiethanolamine, p-dimethylaminophenylalkyl Examples include, but are not limited to, esters.
[0048] Moreover, it is also possible to use a photobase generator, a photoacid generator, etc. as a photopolymerization initiator. One type of these may be used alone, or two or more types may be used in any ratio.
[0049] The photobase generator is not particularly limited, but includes, for example, various compounds that generate primary amines, secondary amines, or tertiary amines, such as cobalt amine complexes, o-acyl oximes, carbamic acid derivatives, Formamide derivatives, sulfonamides (e.g., N-cyclohexyl-4-methylphenylsulfonamide, etc.), quaternary ammonium salts, tosylamines, carbamates (e.g., 2-nitrobenzyl carbamate, 2,5-dinitrobenzylcyclohexyl carbamate, etc.) (1,1-dimethyl-2-phenylethyl-N-isopropylcarbamate, etc.), amine imide compounds, compounds having an amidine structure, α-aminoacetophenone, etc. The photobase generators can be used alone or in combination of two or more.
[0050] Photoacid generators are not particularly limited, but include, for example, diazonium salts, iodonium salts, sulfonium salts, phosphonium salts, selenium salts, metallocene complexes, oxathiazole derivatives, s-triazine derivatives, imide compounds, oxime sulfonates, diazonaphthoquinones, and sulfonic acids. Ester [1-phenyl-1-(4-methylphenyl)sulfonyloxy-1-benzoylmethane, 1,2,3-trisulfonyloxymethylbenzene, 1,3-dinitro-2-(4-phenylsulfonyloxymethyl) benzene, 1-phenyl-1-(4-methylphenyl)sulfonyloxymethyl-1-hydroxy-1-benzoylmethane, disulfone derivatives (diphenyldisulfone, etc.), benzointosylate, etc.] and Lewis acid salts (triphenylsulfonium hexafluoro Antimony, triphenylsulfonium hexafluorophosphate, triphenylsulfonium methanesulfonyl, diphenyl iodohexafluorophosphate, etc. can be used.
[0051] Among these, acetophenones, phosphine oxides, and the like can be preferably used as the photopolymerization initiator.
[0052] The photopolymerization initiators can be used alone or in combination, and can be used in any combination depending on the properties desired for the reaction cured product and the compound that is cured by active energy rays. When using these photopolymerization initiators, the amount used is preferably 0.1 to 50 parts by mass based on 100 parts by mass of the total solid content of the urethane acrylate oligomer.
[0053] Furthermore, a sensitizer can be included. Examples of sensitizers include unsaturated ketones such as chalcone derivatives and dibenzalacetone, 1,2-diketone derivatives such as benzyl and camphorquinone, benzoin derivatives, fluorene derivatives, naphthoquinone derivatives, and anthraquinones. derivatives, polymethine dyes such as xanthene derivatives, thioxanthene derivatives, xanthone derivatives, thioxanthone derivatives, coumarin derivatives, ketocoumarin derivatives, cyanine derivatives, merocyanine derivatives, oxonol derivatives, acridine derivatives, azine derivatives, thiazine derivatives, oxazine derivatives, indoline derivatives , azulene derivatives, azulenium derivatives, squarylium derivatives, porphyrin derivatives, tetraphenylporphyrin derivatives, triarylmethane derivatives, tetrabenzoporphyrin derivatives, tetrapyrazinoporphyrazine derivatives, phthalocyanine derivatives, tetraazaporphyrazine derivatives, tetraquinoxalyloporphyrazine derivatives, naphthalocyanine derivatives, subphthalocyanine derivatives, pyrylium derivatives, thiopyrylium derivatives, tetraphylline derivatives, annulene derivatives, spiropyran derivatives, spirooxazine derivatives, thiospiropyran derivatives, metal arene complexes, organic ruthenium complexes, Michler ketone derivatives, biimidazole derivatives, etc. These include, but are not limited to:
[0054] Urethane acrylate oligomers having polyoxyalkylene chains can be obtained by reacting various polyvalent isocyanates with acrylic esters or methacrylic esters having polyoxyalkylene chains. Specific examples of acrylic esters or methacrylic esters having a polyoxyalkylene chain include BLEMMER PE-90, BLEMMER PE-200, BLEMMER PE-350, and BLEMMER AE-, which are commercially available from NOF Corporation. 90, Blenmar AE-200, Blenmar AE-350, Blenmar PP-500, Blenmar PP-800, Blenmar PP-1000, Blenmar AP-400, Blenmar AP-550, Blenmar AP-800, Blenmar 700PEP-350B, Blenmar 10PEP- 550B, BLEMMER 55PET-400, BLEMMER 30PET-800, BLEMMER 55PET-800, BLEMMER 30PPT-800, BLEMMER 50PPT-800, BLEMMER 70PPT-800, BLEMMER PME-100, BLEMMER PME-200, BLEMMER PME-400, BLEMMER PME- 1000, Blenmar PME-4000, Blenmar AME-400, Blenmar 50POEP-800B, Blenmar 50AOEP-800B, Blenmar AEP, Blenmar AET, Blenmar APT, Blenmar PLE, Blenmar ALE, Blenmar PSE, Blenmar ASE, Blenmar PKE, Blenmar AKE, Blenmar PNE, Blenmar ANE, Blenmar PNP, Blenmar ANP, Blenmar PNEP-600; commercially available products manufactured by Kyoeisha Chemical Co., Ltd., Light Ester 130MA, Light Ester 041MA, Light Ester MTG, Light Acrylate EC-A, Light Acrylate MTG- A, Light Acrylate 130A, Light Acrylate DPM-A, Light Acrylate P-200A, Light Acrylate NP-4EA, Light Acrylate NP-8EA, Light Acrylate EHDG-A; MA-, a commercial product manufactured by Nippon Nyukazai Co., Ltd. 30, MA-50, MA-100, MA-150, RMA-1120, RMA-564, RMA-568, RMA-506, MPG130-MA, AntoxMS-60, MPG-130MA, RMA-150M, RMA-300M, RMA-450M, RA-1020, RA-1120, RA-1820; NK-ESTERM-20G, M-40G, M-90G, M-230G, AMP-, commercial products manufactured by Shin-Nakamura Chemical Co., Ltd. 10G, AMP-20G, AMP-60G, AM-90G, LA; Commercially available products manufactured by Sanyo Chemical Co., Ltd., such as Eleminor RS-30 and RS-30 00.
[0055] (Additives, etc.) The active energy ray composition can be adjusted to a suitable viscosity by diluting it with a solvent, and if necessary, it can also contain inorganic fillers, organic fillers, pigments, film-forming aids, flame retardants, and light diffusion agents commonly used in paints. Agents, plasticizers, solvents, dispersants, wetting agents, thickeners, preservatives, fungicides, light stabilizers, ultraviolet absorbers, antifoaming agents, and the like can be added. As the flame retardant, aluminum phosphate flame retardants are preferred.
[0056] Specific examples of inorganic fillers include inorganic fillers containing oxides, hydroxides, sulfates, carbonates, silicates, etc. of metals such as magnesium, calcium, barium, zinc, zirconium, molybdenum, silicon, and antimony. Examples include fine particles. More detailed examples include inorganic materials containing silica, silica gel, aluminum oxide, aluminum hydroxide, calcium hydroxide, calcium carbonate, magnesium oxide, magnesium hydroxide, aluminosilicate, talc, mica, glass fiber, glass powder, etc. Examples include particle types. One type of inorganic filler may be used, or two or more types may be used in combination.
[0057] Specific examples of organic fillers include polytetrafluoroethylene resin, polyethylene resin, polypropylene resin, polymethyl methacrylate resin, polystyrene resin, polyamide resin, melamine resin, guanamine resin, phenol resin, urea resin, silicone resin, methacrylate resin, Examples include fine polymer particles such as acrylate resin, cellulose powder, nitrocellulose powder, wood powder, waste paper powder, shell powder, and starch. One type of organic filler may be used, or two or more types may be used in combination.
[0058] The insulating layer 12 is made of polyimide (hereinafter also referred to as "specific polyimide") having an aromatic ring concentration of 30% by mass or less and polyamide (hereinafter also referred to as "specific polyamide") having an aromatic ring concentration of 30% by mass or less. It may be formed of a resin whose main component is at least one selected from the group. In other words, the resin constituting the insulating layer 12 may contain only a specific polyimide as a main component, may contain only a specific polyamide as a main component, or may contain a combination of a specific polyimide and a specific polyamide as a main component. May contain.
[0059] (aromatic ring concentration) In this specification, the aromatic ring concentration refers to the content of aromatic rings (the mass ratio of aromatic rings in the raw material of the polymer) contained in polyimide or polyamide (hereinafter also simply referred to as "polymer"), and refers to the aromatic ring content in the polymer. It refers to the value obtained by dividing the weight of the portion corresponding to the ring (hereinafter referred to as "aromatic ring skeleton") by the weight of the entire polymer. That is, the aromatic ring concentration is a value calculated from the composition of monomer components used as raw materials for the polymer. Specifically, the aromatic ring concentration is calculated using the following formula (1). Aromatic ring concentration (mass%) = ["molecular weight of aromatic ring skeleton" x "number of aromatic ring skeletons contained in polymer (polyimide or polyamide)"] / [molecular weight of polymer (polyimide or polyamide)] (Formula 1).
[0060] Note that the molecular weight of the polymer in formula (1) is the number average molecular weight (Mn). In addition, the aromatic ring skeleton in formula (1) includes a fused benzene ring skeleton (molecular weight: 76 g / mol), a fused naphthalene ring skeleton (molecular weight: 128 g / mol), a fused anthracene ring skeleton (molecular weight: 178 g / mol), Refers to a fused aromatic ring skeleton such as a fused phenanthrene ring skeleton (molecular weight: 178 g / mol). The aromatic ring concentration is calculated for each of the fused naphthalene ring skeleton, fused anthracene ring skeleton, and fused phenanthrene ring skeleton as one fused aromatic ring skeleton.
[0061] The aromatic ring concentration is 30% by mass or less, preferably 20% by mass or less, from the viewpoint of improving the tracking resistance of the insulating adhesive tape. Further, the lower limit of the aromatic ring concentration is preferably 5% by mass or more, more preferably 7% by mass or more, and even more preferably 8% by mass or more, from the viewpoint of improving the heat resistance of the insulating adhesive tape. In other words, the aromatic ring concentration is preferably 5% by mass or more and 30% by mass or less, more preferably 7% by mass or more and 20% by mass or less, from the viewpoint of obtaining an insulating adhesive tape that has both tracking resistance and heat resistance. More preferably, it is 8% by mass or more and 20% by mass or less.
[0062] (Functional group concentration (functional group value)) The functional group concentration (acid value or acid anhydride value) of the polymer is not particularly limited, but from the viewpoint of keeping the weight average molecular weight (Mw) of the polymer within the above range, it is preferably 22 mgKOH / g or less, more preferably 14 mgKOH / g or less. , even more preferably 11 mgKOH / g or less, still more preferably 8 mgKOH / g or less. Further, from the above point of view, the lower limit is preferably 5 mgKOH / g or more, more preferably 6 mgKOH / g or more. Note that the functional group concentration can be measured by the method described in Examples described later.
[0063] [Polyimide with an aromatic ring concentration of 30% by mass or less] Polyimide with an aromatic ring concentration of 30% by mass or less (specific polyimide) can be used as a raw material for various tetracarboxylic dianhydrides and polyamine compounds, as long as the proportion of structures derived from aromatic rings to the entire polymer is 30% by mass or less. It is possible to combine these.
[0064] (Tetracarboxylic dianhydride) As the tetracarboxylic dianhydride, one having an aliphatic structure or an alicyclic structure is preferable because the aromatic ring concentration relative to the entire polymer can be easily adjusted to 30% by mass or less.
[0065] Examples of the tetracarboxylic dianhydride having an aliphatic structure include 1,2,3,4-butanetetracarboxylic acid, 1,2,3,4-pentanetetracarboxylic acid, and 1,2,4,5- Examples include tetracarboxylic dianhydrides having a chain hydrocarbon structure such as pentanetetracarboxylic acid, 1,2,3,4-hexanetetracarboxylic acid, and 1,2,5,6-hexanetetracarboxylic acid.
[0066] Examples of the tetracarboxylic dianhydride having an alicyclic structure include cyclobutane-1,2,3,4-tetracarboxylic acid, cyclopentane-1,2,3,4-tetracarboxylic acid, cyclohexane-1, 2,3,4-tetracarboxylic acid, cyclohexane-1,2,4,5-tetracarboxylic acid, 1-carboxymethyl-2,3,5-cyclopentanetricarboxylic acid, 3-(carboxymethyl)-1,2 ,4-cyclopentanetricarboxylic acid (TCA), rel-dicyclohexyl-3,3',4,4'-tetracarboxylic acid, tricyclo[4.2.2.02,5]dec-9-ene-3,4,7,8 -tetracarboxylic acid, 5-carboxymethylbicyclo[2.2.1]heptane-2,3,6-tricarboxylic acid, bicyclo[2.2.1]heptane-2,3,5,6-tetracarboxylic acid, bicyclo[2.2. 2]Oct-7-ene-2,3,6,7-tetracarboxylic acid, bicyclo[3.3.0]octane-2,4,6,7-tetracarboxylic acid, 7,8-diphenylbicyclo[2.2.2 ]oct-7-ene-2,3,5,6-tetracarboxylic acid, 4,8-diphenyl-1,5-diazabicyclooctane-2,3,6,7-tetracarboxylic acid, 9-oxatri Cyclo[4.2.1.02,5]nonane-3,4,7,8-tetracarboxylic acid, 9,14-dioxopentacyclo[8.2.11,11.14,7.02,10.03,8]tetradecane-5,6,12 Cyclo, bicyclo, tricyclotetracarboxylic acids such as ,13-tetracarboxylic acid; spiro ring-containing tetracarboxylic acids such as 2,8-dioxaspiro[4.5]decane-1,3,7,9-teloton;1,3, Alicyclic hydrocarbon structures such as 3a,4,5,9b-hexahydro-5(tetrahydro-2,5-dioxo-3-furanyl)naphtho[1,2-c]furan-1,3-dione (TDA) Examples include tetracarboxylic dianhydrides having the following.
[0067] As the tetracarboxylic dianhydride other than the aliphatic structure or alicyclic structure, a tetracarboxylic dianhydride having an aromatic structure may be used as long as the aromatic ring concentration can be adjusted to 30% by mass or less. Specific examples include pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), and 1,2,3,4-benzenetetracarboxylic dianhydride. 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, diphthalic dianhydride, and the like. Among these, PMDA and BPDA are preferred.
[0068] The above-mentioned tetracarboxylic dianhydrides having an aliphatic structure, an alicyclic structure, or an aromatic structure may be used alone, or two or more types may be used in combination. Moreover, the examples of the monomers may have a substituent as appropriate. Examples of the substituent include an alkyl group, a halogen atom, a nitro group, and a cyano group. Further, in place of the above-mentioned tetracarboxylic dianhydride, a tetracarboxylic acid derivative such as a tetracarboxylic acid or a tetracarboxylic acid diester having a similar structure may be used.
[0069] (Polyamine compound) Similarly to the above-mentioned tetracarboxylic dianhydride, the polyamine compound is preferably one having an aliphatic structure or an alicyclic structure because the aromatic ring concentration relative to the entire polymer can be easily adjusted to 30% by mass or less. Among these, dimer diamine (DDA), which is a polyamine compound having a dimer structure, is preferred.
[0070] As the dimer diamine, a compound obtained by converting the carboxyl group of dimer acid into an amino group can be used. Dimer acid is a polybasic acid compound with a dimer structure, and is a dimer of fatty acids (hereinafter referred to as (referred to as "fatty acid dimer").
[0071] The fatty acid dimer is preferably a compound having 20 to 60 carbon atoms, more preferably a compound having 24 to 56 carbon atoms, even more preferably a compound having 28 to 48 carbon atoms, and even more preferably a compound having 36 to 44 carbon atoms. The fatty acid dimer is preferably a dicarboxylic acid compound having a branched structure obtained by subjecting fatty acids to a Diels-Alder reaction. The fatty acid is preferably an unsaturated fatty acid having 10 to 30 carbon atoms, more preferably an unsaturated fatty acid having 10 to 24 carbon atoms. The unsaturated fatty acid has one or more carbon-carbon double bonds or carbon-carbon triple bonds. Specific examples of the fatty acids include natural fatty acids such as soybean oil fatty acids, tall oil fatty acids, and rapeseed oil fatty acids, as well as oleic acid, linoleic acid, linolenic acid, erucic acid, etc. that are purified from these fatty acids. The branched structure is preferably an aliphatic chain structure or a ring structure, and more preferably a ring structure. The ring structure preferably has one or more aromatic rings and an alicyclic structure, and more preferably one or more alicyclic structures. The alicyclic structure may have one double bond in the ring or may have no double bond.
[0072] When fatty acid dimers are synthesized, in addition to fatty acid dimers, fatty acid trimers and, in some cases, tetramers are also produced. Therefore, a polybasic acid compound containing a dimer skeleton is a mixture containing not only a fatty acid dimer as a main component but also a trimer of fatty acids and, in some cases, a fatty acid as a raw material. The content of fatty acid dimer in the dimer acid is preferably 70% by mass or more, more preferably 90% by mass or more, and still more preferably 95% by mass or more.
[0073] Since dimer acid uses unsaturated fatty acids as raw materials, unsaturated bonds may remain. In such a case, hydrogenation (also referred to as hydrogenation reaction) can be performed to suppress the number of unsaturated bonds. This improves the reaction stability when synthesizing the specific polyimide, and further improves the heat resistance of the insulating adhesive tape containing the specific polyimide.
[0074] Commercially available dimer acids include, for example, "Pripol 1004", "Pripol 1006", "Pripol 1009", "Pripol 1013", "Pripol 1015", "Pripol 1017", "Pripol 1022", and "Pripol 1022" manufactured by Croda Japan. "Pripol 1025", "Pripol 1040"; "Enpol 1008", "Enpol 1012", "Enpol 1016", "Enpol 1026", "Enpol 1028", "Enpol 1043", "Enpol 1061", " Empol 1062'' etc. Each of these may be used alone, or two or more types may be used in combination.
[0075] The dimer diamine is preferably a compound having 20 to 60 carbon atoms, more preferably a compound having 24 to 56 carbon atoms, even more preferably a compound having 28 to 48 carbon atoms, and even more preferably a compound having 36 to 44 carbon atoms. A dimer diamine having such a carbon number is preferable from the viewpoint of easy availability.
[0076] Commercial products of dimer diamine (DDA) include, for example, "PRIAMINE 1071", "PRIAMINE 1073", "PRIAMINE 1074", "PRIAMINE 1075" manufactured by Croda Japan, and "VERSAMINE 551" manufactured by BASF Japan. can be mentioned. Each of these may be used alone, or two or more types may be used in combination.
[0077] Note that the polybasic acid compound having a dimer structure for obtaining a dimer diamine can have a plurality of structures during the synthesis process, but is not limited to this structure.
[0078] Polyamine compounds other than dimer diamine (hereinafter also referred to as "other diamines") are not particularly limited, but include, for example, aliphatic structures (unsaturated bonds) that may have substituents. Examples include diamine compounds having a chain hydrocarbon structure and / or alicyclic hydrocarbon structure (which may contain an aromatic ring and / or an alicyclic hydrocarbon structure), and an aromatic structure (an aromatic ring and the above structures may be arbitrarily combined).
[0079] The dimer structure (dimer diamine) and polyamine compounds other than dimer diamine (other diamines) may be used alone, or two or more types may be used in combination.
[0080] (Other monomers) As a raw material for the resin component constituting the insulating layer 12, monomers other than those described above may be used within a range that does not impede the object of the present invention. For example, a polyamine compound having three or more amino groups may be used. Examples of the polyamine compound having three or more amino groups include 1,2,4-triaminobenzene, 3,4,4'-triamino diphenyl ether, and the like.
[0081] (Crosslinking agent) The specific polyimide can improve the heat resistance of the insulating layer 12 by reacting with a crosslinking agent and crosslinking it. Therefore, it is preferable that the monomer component used as a raw material for the specific polyimide contains a crosslinking agent.
[0082] Examples of the crosslinking agent include compounds that have two or more reactive functional groups in one molecule and can construct a crosslinked structure. Specific examples include epoxy compounds, cyanate ester compounds, isocyanate group-containing compounds, chelate compounds, carbodiimide group-containing compounds, and the like.
[0083] The epoxy compound refers to a compound having two or more epoxy groups in one molecule, and known compounds can be used.
[0084] Examples of epoxy compounds include bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, novolak epoxy resin, dicyclopentadiene epoxy resin, polyfunctional phenol epoxy resin, naphthalene epoxy resin, and aralkyl-modified epoxy resin. Type epoxy resins, alicyclic and alcohol-based glycidyl ethers, alicyclic and alcohol-based glycidyl amines (for example, "Tetrad C" and "Tetrad X" manufactured by Mitsubishi Gas Chemical Co., Ltd.) , and glycidyl ester resins such as alicyclic and alcohol resins.
[0085] The crosslinking agent may be a low molecular compound or a high molecular compound. Moreover, the crosslinking agent itself may be a thermosetting compound, or may be a compound in which the crosslinking agent and the specific polyimide are crosslinked. Each of the crosslinking agents may be used alone, or two or more types may be used in combination.
[0086] (functional group) The specific polyimide preferably has a functional group because heat resistance can be improved by crosslinking by reacting with the crosslinking agent.
[0087] Examples of the functional group include a carboxyl group, an amino group, a hydroxyl group, and an acid anhydride group. These may be functional groups derived from monomers used as raw materials for the specific polyimide, or functional groups may be introduced as modified products after obtaining the polymer. In addition to the embodiment in which the functional group is located at the end of the polymer, there are embodiments in which the functional group is present in a side group and / or a side chain. A preferred example is an embodiment in which the polymer has a functional group such as a carboxyl group, an acid anhydride group, or an amino group at the terminal end. Further, examples include embodiments in which the side group or side chain has at least one type of functional group such as a carboxyl group, an amino group, or a hydroxyl group.
[0088] When having a hydroxyl group as a functional group, a phenolic hydroxyl group is suitable. By having a phenolic hydroxyl group, it is possible to build a crosslinked structure with a crosslinking agent and form a tough insulating layer. A phenolic hydroxyl group can be easily introduced by using a polybasic acid compound having a phenolic hydroxyl group and / or a polyamine compound having a phenolic hydroxyl group. The aromatic ring of this phenolic hydroxyl group is preferably included in the main chain skeleton. Moreover, it is preferable to use a polybasic acid compound having a phenolic hydroxyl group.
[0089] (catalyst) A catalyst may be used when the specific polyimide and the crosslinking agent are reacted and crosslinked. Examples of catalysts include aliphatic tertiary amines such as triethylamine; aromatic tertiary amines such as dimethylaniline; heterocyclic tertiary amines such as pyridine, picoline, and isoquinoline; and phosphorus compounds. . Specific examples include 1,8-diazabicyclo[5,4,0]-undecene-7 (DBU) and triphenylphosphine (TPP).
[0090] [Method for producing polyimide with an aromatic ring concentration of 30% by mass or less] A polyimide (specific polyimide) having an aromatic ring concentration of 30% by mass or less can be produced by various known methods. Specific examples include a method in which a polyamic acid resin or a polyamic acid ester resin, which is a polyimide precursor, is cyclized by heating and converted into an imide group.
[0091] Examples of the method for synthesizing the polyamic acid resin include a method in which a tetracarboxylic dianhydride and a diamine are reacted. Specifically, monomer components containing tetracarboxylic dianhydride and diamine are dissolved in a solvent, stirred for 0.1 to 2 hours at a temperature of 60 to 120°C, and polymerized to form a polyimide precursor. A polyamic acid resin can be produced.
[0092] A method for synthesizing polyamic acid ester resin is, for example, a method of obtaining a diester using tetracarboxylic dianhydride and alcohol, and then reacting it with a diamine in the presence of a condensing agent; The remaining dicarboxylic acid is then converted into acid chloride and reacted with a diamine. Thereby, a polyamic acid ester resin which is a polyimide precursor can be manufactured.
[0093] Examples of organic solvents used in polymerization include N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAc). ), N,N-diethylacetamide, hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diglyme, triglyme, cresol and the like. The organic solvents may be used alone or in combination of two or more. Furthermore, the organic solvent can also be used in combination with aromatic hydrocarbons such as xylene and toluene.
[0094] The method of cyclizing the polyimide precursor by heating to convert it into an imide group, that is, the method of imidizing the polyimide precursor to obtain a polyimide resin, is not particularly limited, but for example, a method of cyclizing the polyimide precursor by heating and converting it into an imide group is carried out in a solvent at a temperature of 80 to 400°C. An example is a method of heating for 0.5 to 50 hours. At this time, a catalyst and / or a dehydrating agent may be used if necessary.
[0095] Examples of the catalyst include aliphatic tertiary amines such as triethylamine; aromatic tertiary amines such as dimethylaniline; and heterocyclic tertiary amines such as pyridine, picoline, and isoquinoline. Examples of the dehydrating agent include aliphatic acid anhydrides such as acetic anhydride, aromatic acid anhydrides such as benzoic anhydride, and the like.
[0096] The imidization rate (imide ring formation rate) of the specific polyimide is not particularly limited, but it From the viewpoint of forming an insulating layer that imparts tracking resistance, it is preferably 80% or more, more preferably 90% or more, and still more preferably 95 to 100%. The imidization rate can be determined by NMR, IR analysis, etc.
[0097] [Polyamide with an aromatic ring concentration of 30% by mass or less] A polyamide (specific polyamide) having an aromatic ring concentration of 30% by mass or less is a polymer containing a repeating structural unit containing an amide group. Specifically, the specific polyamide is a polybasic acid compound, a polyamine compound, a polymer of other monomers as necessary, or a modified product obtained by modifying the polymer. Here, the modified product is a derivative obtained by partially converting the molecular structure of the polymer (for example, converting a functional group, substituting with another compound, or adding another compound). For the specific polyamide, various polybasic acid compounds, polyamine compounds, and the like can be combined as raw materials, as long as the proportion of structures derived from aromatic rings to the entire polymer is 30% by mass or less.
[0098] In order to adjust the aromatic ring concentration to 30% by mass or less, it is preferable to introduce a dimer structure into the polyamide resin. A monomer having a dimer structure may be used to introduce the dimer structure into the polyamide resin. A dimer acid is suitable as the polybasic acid compound having a dimer structure. Examples of the dimer acid include those similar to the fatty acid dimer exemplified in the specific polyimide. Further, as the polyamine compound having a dimer structure, dimer diamine is suitable. Examples of the dimer diamine include the same dimer diamines as exemplified in the specific polyimide.
[0099] (polybasic acid compound) Polybasic acid compounds are dibasic acids or higher carboxylic acids. A part of the polybasic acid compound may be an acid anhydride. Examples of the polybasic acid compound include the aforementioned dimer acid and other polybasic acid compounds.
[0100] Other polybasic acid compounds are polybasic acid compounds other than the dimer acid, and are bifunctional or higher functional compounds.
[0101] Examples of dibasic acid compounds include phthalic acid, isophthalic acid, terephthalic acid (TPA), 1,4-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, benzophenone-4,4'-dicarboxylic acid, 4,4' - Aromatic dibasic acids such as biphenyldicarboxylic acid; oxalic acid, malonic acid, methylmalonic acid, succinic acid, glutaric acid, adipic acid, maleic acid, fumaric acid, malic acid, tartaric acid, thiomalic acid, pimelic acid, suberin Aliphatic dibasic acids such as azelaic acid, sebacic acid, dodecanedioic acid, hexadecanedionic acid, diglycolic acid; 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid Examples include alicyclic dibasic acids such as acids. Among the dibasic acid compounds, isophthalic acid, terephthalic acid (TPA) and 1,4-cyclohexanedicarboxylic acid are preferred.
[0102] Examples of trifunctional or higher polybasic acid compounds include trimellitic acid, hydrogenated trimellitic acid, pyromellitic acid, hydrogenated pyromellitic acid, trimesic acid, 1,4,5,8-naphthalenetetracarboxylic acid, etc. It will be done.
[0103] In addition, preferred examples of other polybasic acid compounds include polybasic acid compounds having a phenolic hydroxyl group. By using a polybasic acid compound having a phenolic hydroxyl group, a tough insulating layer can be formed. A polybasic acid compound having a phenolic hydroxyl group is a compound having a phenolic hydroxyl group and two or more acidic functional groups. Examples of the acidic functional groups include carboxyl groups.
[0104] Examples of polybasic acid compounds having a phenolic hydroxyl group include monohydroxyisophthalic acids such as 2-hydroxyisophthalic acid, 4-hydroxyisophthalic acid, and 5-hydroxyisophthalic acid (5-HIP); 2,5-dihydroxyisophthalic acid; Dihydroxyisophthalic acids such as 2,4-dihydroxyisophthalic acid and 4,6-dihydroxyisophthalic acid; Monohydroxyterephthalic acids such as 2-hydroxyterephthalic acid; 2,3-dihydroxyterephthalic acid, 2,6-dihydroxyterephthalic acid, etc. Dihydroxyterephthalic acid; Hydroxyphthalic acids such as 3-hydroxyphthalic acid and 4-hydroxyphthalic acid; 3,4-dihydroxyphthalic acid, 3,5-dihydroxyphthalic acid, 4,5-dihydroxyphthalic acid, 3,6-dihydroxy Examples include dihydroxyphthalic acids such as phthalic acid. Among these, 5-hydroxyisophthalic acid (5-HIP) is preferred in terms of copolymerizability, ease of availability, and the like. In addition, in the polybasic acid compound having a phenolic hydroxyl group, the carboxyl group of the compound exemplified above may form an acid anhydride group, or the carboxyl group may form an ester.
[0105] The dimer acid and other polybasic acid compounds exemplified as polybasic acid compounds may be used alone, or two or more types may be used in combination.
[0106] (Crosslinking agent) By reacting with a crosslinking agent and crosslinking the specific polyamide, it is possible to improve the heat resistance of the insulating layer. Therefore, it is preferable that the monomer component used as a raw material for the specific polyamide contains a crosslinking agent. Examples of the crosslinking agent include the same crosslinking agents as those exemplified above for the specific polyimide.
[0107] (functional group) The specific polyamide preferably has a functional group because heat resistance can be improved by crosslinking by reacting with the crosslinking agent. Examples of the functional group include the same functional groups as those exemplified in the specific polyimide, and a phenolic hydroxyl group is preferred.
[0108] (others) The specific polyamide may be a polyamideimide partially containing an imide group, or a polyamide ester partially containing an ester group, within a range that does not impede the object of the present invention.
[0109] [Method for producing polyamide with aromatic ring concentration of 30% by mass or less] A polyamide (specific polyamide) having an aromatic ring concentration of 30% by mass or less can be produced by various known methods. As specific examples, synthesis can be performed by melt polymerization, interfacial polymerization, solution polymerization, bulk polymerization, solid phase polymerization, or a combination of these. Among these, solution polymerization is preferred.
[0110] The specific polyamide polymer can be produced in the presence or absence of a catalyst using a monomer component containing a polybasic acid compound, a polyamine compound, and other monomers as necessary. . For example, a predetermined amount of dimer acid, other acid monomers, dimer diamine, other amine monomers, and ion-exchanged water are placed in a flask filled with nitrogen, and the mixture is uniformly dissolved or dispersed by heating and stirring at 20 to 100°C. Thereafter, the temperature is gradually raised to 230°C while removing the ion-exchanged water and water generated by the reaction, and upon reaching 230°C, the pressure is reduced to about 15 mmHg, and this state is maintained for about 1 hour to obtain the specified polyamide. be able to. The heating temperature is, for example, 150 to 300°C. Heating time is about 1 to 24 hours. In order to accelerate the synthesis reaction, it is preferable to perform a dehydration or dealcoholization reaction. Furthermore, in order to avoid coloration and decomposition reactions due to high temperatures, it is preferable to carry out the reaction at 180 to 270°C under reduced pressure.
[0111] The specific polyimide and specific polyamide may be used alone, or two or more types may be used in combination. Among the specific polyimides and specific polyamides, specific polyimides are more preferred from the viewpoint of obtaining an insulating adhesive tape that has both tracking resistance and heat resistance.
[0112] The resin component constituting the insulating layer may contain resins other than the specific polyimide and the specific polyamide within a range that does not impede the object of the present invention. Other resins that can be used together with the specific polyimide and / or the specific polyamide include fluororesins and the like.
[0113] The insulating composition containing the specific polyimide and / or the specific polyamide can be adjusted to a suitable viscosity by using the above-mentioned crosslinking agent and solvent, and may also contain inorganic fillers, organic fillers, etc. commonly used in paints, if necessary. Adding pigments, film-forming aids, flame retardants, light diffusing agents, plasticizers, dispersants, wetting agents, thickeners, preservatives, fungicides, light stabilizers, ultraviolet absorbers, antifoaming agents, etc. Can be done. As the flame retardant, aluminum phosphate flame retardants are preferred.
[0114] [Adhesive layer] The adhesive layer is formed by applying and curing an adhesive composition, and is a layer for imparting adhesiveness. As shown in FIG. 1(2), the insulating adhesive tape 1 constitutes the other outermost layer from the insulating layer 12, and is subdivided into an adhesive impregnated layer 13b impregnated into the glass cloth layer 11 and an adhesive non-impregnated layer 13a that is not impregnated. Ru. Note that if the insulating layer 12 impregnates the entire glass cloth layer, the adhesive impregnated layer 13b may not be present.
[0115] The adhesive composition for forming the adhesive layer mainly contains an adhesive, and examples of the adhesive include an acrylic adhesive, a silicone adhesive, a rubber adhesive, a urethane adhesive, and the like. Each of these may be used alone, or two or more types may be used in combination. Among these, silicone adhesives are preferred from the viewpoint of heat resistance, from the viewpoints of heat resistance, stability over time, no silicone contamination, and ease of delicate adjustment of adhesive strength with insulation varnish resistance, etc. Acrylic adhesives are more preferred. An adhesive composition is obtained by adding a crosslinking agent, additives, etc. to the adhesive as necessary and mixing them thoroughly. Further, the viscosity can be adjusted to be suitable for coating by diluting with a solvent.
[0116] As the silicone adhesive, a material known as a silicone resin can be used. Specifically, triorganosiloxane represented by R3SiO0.5 (where R represents a substituted or unsubstituted monovalent hydrocarbon group) in the molecule is added to organopolysiloxane having silanol groups at both ends of the molecular chain. Examples include those obtained by partially dehydrating and condensing organopolysiloxanes having units and SiO2 units. These are available as silicone adhesives KR-101-10, KR-120, KR-130, and X-40-3068 (all manufactured by Shin-Etsu Chemical Co., Ltd.). There are two general curing methods for silicone adhesives: one using peroxides such as benzoyl peroxide, and the other using a reaction between a platinum catalyst and an organopolysiloxane having Si--H bonds. Can be used or used together.
[0117] The acrylic adhesive preferably contains a (meth)acrylic acid ester polymer. In other words, the adhesive composition used as a raw material for an acrylic adhesive contains a (meth)acrylic acid ester polymer. In addition, in this specification, (meth)acrylic acid means acrylic acid and / or methacrylic acid. Moreover, in this specification, the concept of "copolymer" is also included in "polymer".
[0118] ((meth)acrylic acid ester polymer) The (meth)acrylic acid ester polymer contains (meth)acrylic acid alkyl ester whose alkyl group has 1 to 20 carbon atoms as a monomer unit constituting the polymer. Favorable adhesiveness can be developed. Examples of the (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate [BA, BMA], and (meth)acrylate. ) n-pentyl acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate [2-EHA, 2-EHMA], isooctyl (meth)acrylate, n-decyl (meth)acrylate, Examples include n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, and stearyl (meth)acrylate. Each of these may be used alone, or two or more types may be used in combination. Among these, from the viewpoint of improving the adhesiveness of the insulating adhesive tape, (meth)acrylic acid esters in which the alkyl group has 1 to 8 carbon atoms are preferred, and n-butyl (meth)acrylate [BA, BMA] and 2-ethylhexyl (meth)acrylate [2-EHA, 2-EHMA] is more preferred, and n-butyl acrylate [BA] and 2-ethylhexyl acrylate [2-EHA] are even more preferred.
[0119] The (meth)acrylic acid ester polymer preferably contains 50% by mass or more of (meth)acrylic acid alkyl ester in which the alkyl group has 1 to 20 carbon atoms as a monomer unit constituting the polymer, and 60% by mass or more. The content is more preferably 70% by mass or more, and even more preferably 70% by mass or more. By containing the (meth)acrylic acid alkyl ester in an amount of 50% by mass or more, the (meth)acrylic acid ester polymer can exhibit suitable adhesiveness. Further, the (meth)acrylic acid ester polymer preferably contains 90% by mass or less of (meth)acrylic acid alkyl ester having an alkyl group having 1 to 20 carbon atoms as a monomer unit constituting the polymer, It is more preferable that the content is 80% by weight or less. By containing the (meth)acrylic acid alkyl ester at 90% by mass or less, other monomer components can be introduced into the (meth)acrylic ester polymer in suitable amounts.
[0120] The (meth)acrylic acid ester polymer is a reactive functional group that imparts adhesive properties and cohesive force to the (meth)acrylic acid alkyl ester whose main alkyl group has 1 to 20 carbon atoms. A copolymer obtained by copolymerizing a monomer containing a group (hereinafter referred to as a "reactive functional group-containing monomer") is preferable.
[0121] Examples of reactive functional group-containing monomers include monomers having a carboxy group in the molecule (hereinafter referred to as "carboxy group-containing monomer"), monomers having a hydroxyl group in the molecule (hereinafter referred to as "hydroxyl group-containing monomer"), and monomers having an amino group in the molecule. (hereinafter referred to as "amino group-containing monomer"). Each of these may be used alone, or two or more types may be used in combination.
[0122] Examples of the carboxy group-containing monomer include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. These may be used alone or in combination of two or more. Among these, acrylic acid is preferred. According to acrylic acid, the above effects are even more excellent.
[0123] The (meth)acrylic acid ester polymer preferably contains a carboxy group-containing monomer in an amount of 0.5% by mass or more, more preferably 1% by mass or more, and 3% by mass or more as a monomer unit constituting the polymer. It is even more preferable to contain it. In addition, the (meth)acrylic acid ester polymer preferably contains a carboxy group-containing monomer in an amount of 30% by mass or less, more preferably 25% by mass or less, and 20% by mass or less, as a monomer unit constituting the polymer. % or less is more preferable.
[0124] Examples of hydroxyl group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and )3-Hydroxybutyl acrylate , (meth)acrylic acid hydroxyalkyl esters such as 4-hydroxybutyl (meth)acrylate, and the like. These may be used alone or in combination of two or more.
[0125] Examples of the amino group-containing monomer include aminoethyl (meth)acrylate and n-butylaminoethyl (meth)acrylate. These may be used alone or in combination of two or more.
[0126] The polymerization mode of the (meth)acrylic acid ester polymer may be a random copolymer or a block copolymer.
[0127] The weight average molecular weight of the (meth)acrylic acid ester polymer is preferably 200,000 or more, more preferably 300,000 or more, and even more preferably is 400,000 or more, more preferably 500,000 or more. Further, the upper limit thereof is preferably 2.5 million or less, more preferably 2 million or less, still more preferably 1.5 million or less, and even more preferably 1.2 million or less, from the viewpoint of improving the adhesive strength of the resulting pressure-sensitive adhesive. Note that the weight average molecular weight in this specification is a value measured by gel permeation chromatography (GPC) in terms of standard polystyrene.
[0128] (Crosslinking agent) The crosslinking agent may be one that reacts with the reactive functional group of the (meth)acrylic acid ester polymer, such as isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, Examples include aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, ammonium salt crosslinking agents, and the like. Each of these may be used alone, or two or more types may be used in combination. Among these, isocyanate-based crosslinking agents are preferred. In this case, the (meth)acrylic acid ester polymer preferably contains at least one carboxy group- or hydroxyl group-containing monomer as a monomer unit constituting the polymer. The adhesive obtained in combination with an isocyanate-based crosslinking agent greatly increases the interfacial strength with the glass cloth layer. As a result, it is possible to produce a tape (cellophane tape-like wound product) that is directly wound without using a release liner, which is advantageous in terms of processability and self-releasability.
[0129] The isocyanate crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate; aliphatic polyisocyanates such as hexamethylene diisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate; and their biuret forms, isocyanurate forms, and adduct forms which are reactants with low-molecular active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil. Each of these may be used alone, or two or more types may be used in combination. Among these, from the viewpoint of reactivity with hydroxyl groups, trimethylolpropane-modified aromatic polyisocyanates are preferred, trimethylolpropane-modified tolylene diisocyanates and trimethylolpropane-modified xylylene diisocyanates are more preferred, and trimethylolpropane-modified tolylene diisocyanates are more preferred. More preferred are diisocyanates.
[0130] The content of the isocyanate crosslinking agent in the adhesive composition is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, based on 100 parts by mass of the (meth)acrylic acid ester polymer. Further, the upper limit of the content is preferably 10 parts by mass or less, and is adjusted in consideration of adhesive strength. By using an isocyanate-based crosslinking agent, the tightness with the glass cloth layer is improved. Adhesion is improved, and problems such as adhesive residue and peeling from the support during processing can be reduced.
[0131] (Additives, etc.) Various additives commonly used in acrylic adhesives can be added to the adhesive composition within a range that does not impede the object of the present invention. Examples of various additives include tackifiers, antioxidants, softeners, fillers, flame retardants, and the like. Note that the polymerization solvent and dilution solvent described below are not included in the additives constituting the adhesive composition. The flame retardant is preferably an aluminum phosphate flame retardant.
[0132] [Method for manufacturing insulating adhesive tape] Although the method for manufacturing the insulating adhesive tape according to the present embodiment is not particularly limited, for example, when manufacturing an insulating adhesive tape 1 as shown in FIG. By coating and curing to obtain an adhesive layer, and laminating the adhesive layer to a glass cloth, an adhesive layer having an adhesive non-impregnated layer 13a that is not impregnated into the glass cloth and an adhesive impregnated layer 13b that is impregnated with the glass cloth is obtained. 13 and the glass cloth layer 11 is manufactured. Next, an insulating composition is applied to the surface of the laminate a opposite to the surface on which the adhesive layer 13 is provided via the glass cloth layer 11, dried, and cured to form a structure as shown in FIG. 1(2). An insulating layer 12 having an insulating non-impregnated layer 12a not impregnated with the glass cloth layer 11 and an insulating impregnated layer 12b impregnated with the glass cloth layer 11, and an adhesive layer 13 having an adhesive impregnated layer 13b similarly impregnated with the glass cloth layer 11. An insulating adhesive tape 1 having a structure including an adhesive layer 13 having a structure of 13 and a glass cloth layer 11 between the insulating layer 12 and the adhesive layer 13 can be manufactured on a release film. From the viewpoint of obtaining an insulating adhesive tape without voids, it is desirable to adjust the viscosity of the insulating composition, apply the insulating composition directly to glass cloth to impregnate it, and then dry it. The above-mentioned tape may be wound around a cylindrical core material together with a release film in the form of a roll. If necessary, the release film is peeled off from the adhesive layer 13 and the core material is wrapped so that the adhesive layer 13 and the insulating layer 12 are in contact with each other. It is also possible to form a roll-like form by laminating them while winding them.
[0133] In addition, by first coating an insulating composition on a release film, drying it, and curing it after laminating the glass cloth, the insulating layer 12 having the insulating non-impregnated layer 12a and the insulating impregnated layer 12b and the glass cloth are formed. After obtaining the laminate b with the layer 11, an insulating adhesive tape having a release film on the insulating layer 12 side can be manufactured by applying the adhesive composition to a glass cloth, drying, and curing it. The above-mentioned tape can also be formed into a roll by peeling off the release film from the insulating layer 12 as needed, and laminating it around a core material so that the adhesive layer 13 and the insulating layer 12 are in contact with each other.
[0134] In addition, glass cloth should be subjected to surface treatment such as primer treatment, corona treatment, plasma treatment, etc. in order to improve adhesion with insulating compositions or adhesive compositions and reduce voids during drying. You may.
[0135] The coating liquid for the insulating layer and the adhesive layer may be applied by a conventional method, such as bar coating, knife coating, Mayer bar coating, roll coating, blade coating, die coating, gravure coating, and dip coating. etc.
[0136] The drying and curing conditions for the insulating composition are as follows: If it is an insulating composition whose main component is urethane acrylate, it is dried by removing the solvent at 80 to 150°C, and then dried with a high-pressure mercury lamp at an intensity of 120 mW / cm2 and an integrated light amount of 1000 mJ / cm. Preferably cured in cm2. If it is an insulating composition containing polyimide or polyamide as a main component, it is preferable to dry it by removing the solvent and cure it with a crosslinking agent at a temperature of 100 to 200°C for 2 to 5 minutes.After drying, it is further dried at room temperature to 5 minutes. It is more preferable to age for about 1 hour to 5 days in an environment of about 50°C.
[0137] Regarding the drying and curing conditions for the adhesive composition, it is preferable to dry and harden the adhesive composition by removing the solvent in hot air at 120 to 200°C for 5 minutes, regardless of whether it is a peroxide-curing type or an addition-curing type. Furthermore, it is more preferable to carry out aging for about 1 hour to 5 days in an environment of room temperature to about 50°C. For acrylic adhesives, it is preferable to dry and harden by removing the solvent with hot air at 80°C to 150°C for 1 to 5 minutes, and then aging for 1 hour to 5 days in an environment of room temperature to 50°C. It is more preferable to do so.
[0138] Films used for release films include polyester films made of polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, polyolefin films made of polyolefins such as polyethylene, polypropylene, and polymethylpentene, polycarbonate films, and polyvinyl acetate. Examples include plastic films such as films, paper films such as pulp, or laminates made of layers of two or more of these materials, and the film may be treated with a release agent. .
[0139] (Other layers) When the product form is such that the insulating adhesive tape 1 shown in FIG. 1 is wound around a core material, the adhesive layer 13 and the insulating layer 12 as a surface layer are in direct contact. Therefore, if necessary, a release layer may be formed by coating the surface layer of the insulating layer 12 with a release agent so that the insulating layer 12 and the adhesive layer 13 can be separated cleanly at the interface.
[0140] Materials that impart release properties and are used as raw materials for the release layer include silicone release agents, long-chain alkyl pendant polymers in which alkyl groups having 16 to 24 carbon atoms are arranged in a pendant manner through ester groups or ether groups. Examples include fluorine-based release agents, fluorine-based release agents, and the like.
[0141] <Other embodiments>
[0142] In the present invention, it is also preferable to form an insulating adhesive tape having a thermoplastic resin layer from the viewpoint of improving handling properties such as cutting and punching of the insulating adhesive tape and toughness of the tape when applying it to an object. The thermoplastic resin layer may be located between the glass cloth layer and the insulating layer as shown in FIG. 4 (Embodiment 2), or be located between the glass cloth layer and the adhesive layer as shown in FIG. 5 (Embodiment 2). 3) is preferred. Furthermore, in order to improve the bonding strength between the thermoplastic resin layer and the glass cloth layer in Embodiment 2, an adhesive layer 15 may be formed between the glass cloth layer and the thermoplastic resin layer as shown in FIG. Embodiment 4). In Embodiment 3, in order to improve the bonding strength between the thermoplastic resin layer and the glass cloth layer, an adhesive layer 15 may be formed between the glass cloth layer and the thermoplastic resin layer as shown in FIG. Five). In Embodiments 2 and 3, for example, a thermoplastic resin film is heated to a semi-molten state, and then laminated and bonded to the glass cloth layer 11 to form a laminate of the glass cloth layer 11 / thermoplastic resin layer 14. Later, it can be formed by laminating the insulating layer 12 and the adhesive layer 13. In embodiment 4 and embodiment 5, for example, the adhesive layer 15 is formed on the thermoplastic resin layer 14, and the glass cloth layer 11 is laminated and bonded, so that the glass cloth layer 11 / adhesive layer 15 / thermoplastic It can be formed by laminating the insulating layer 12 and the adhesive layer 13 after forming the resin layer 14 into a laminate. Note that it is also preferable that the pressure-sensitive adhesive layer 15 in Embodiment 5 is replaced with the pressure-sensitive adhesive layer 13.
[0143] The thickness of the thermoplastic resin layer 14 in Embodiments 2 to 5 is preferably 5 to 50 μm, and preferably 10 to 30 μm because it can be formed without affecting tracking resistance. The thickness of the adhesive layer 15 is sufficient as long as the thermoplastic resin layer can be bonded to other layers, and is preferably 1 to 15 μm as long as it does not affect tracking resistance.
[0144] The thermoplastic resin film in the thermoplastic resin layer 14 may be any thermoplastic resin that can be manufactured into a film, and any known resin can be used. For example, polyethylene resin, polypropylene resin, polybutadiene resin, cyclic olefin resin, polymethylpentene resin, polystyrene resin, ethylene vinyl acetate copolymer, ethylene vinyl alcohol copolymer resin, ethylene acrylate copolymer, acrylonitrile-styrene resin, acrylonitrile-styrene resin, Chlorinated polystyrene / styrene copolymer resin, acrylonitrile / acrylic rubber / styrene copolymer resin, acrylonitrile / butadiene / styrene copolymer resin, silicone resin, acetate resin, cellulose acetate resin, methacrylic resin, acrylic resin, vinyl chloride resin, chlorinated Polyethylene resin, fluorinated polyethylene resin, polyvinylidene fluoride resin, nylon resin, polyacetal resin, polyester resin, polyethylene terethalate resin, polyethylene naphthalate resin, polybutylene terethalate resin, polycarbonate resin, modified polyphenylene ether resin, thermoplastic polyurethane elastomer , polyphenylene sulfide resin, polyetheretherketone resin, liquid crystal polymer, polytetrafluoroethylene resin, polyfluoroalkoxy resin, polyetherimide resin, polysulfone resin, polyketone resin, thermoplastic polyimide resin, polyamideimide resin, polyarylate resin, polysulfone Examples include resin, polyether sulfone resin, biodegradable resin, and biomass resin, and refers to those made into a film. In particular, a thermoplastic resin film made of polyethylene teretalate resin, which is highly smooth and inexpensive, can be suitably used.
[0145] The adhesive used for the adhesive layer 15 may be any known adhesive as long as it can bond the thermoplastic resin layer 14 to other layers, such as acrylic resin, polyester resin, epoxy resin, or urethane resin. , adhesives made by curing silicone resins and the like. Commercially available products include polyester adhesive TM-K76 (curing agent CAT-RT85) manufactured by Toyo Morton Co., Ltd. The composition of the adhesive layer 15 and the adhesive layer 13 may be the same or different.
[0146] The insulating layer 12 and adhesive layer 13 in Embodiments 2 to 5 may be made of the same materials as those described in FIG. 1.
[0147] The insulating adhesive tape of the present invention may further contain a layer in order to provide functions (characteristics) depending on the intended use within a range that does not impede the object of the present invention. For example, a heat dissipation layer, a water vapor barrier layer, an electromagnetic wave absorption layer, a design layer by printing or coloring, and a polarizing layer may be provided as necessary. However, even in this case, it is necessary that the glass cloth be impregnated with the cured product of the insulating composition or the cured product of the adhesive composition. Further, on the surface layer of the insulating layer 12, for example, a protective layer or the like may be formed to protect the surface of the insulating layer 12 within a range that does not impede the object of the present invention.
Example
[0148] The present disclosure will be described below based on examples. Note that the present disclosure is not limited to the following examples, and the following examples can be modified and changed based on the spirit of the present disclosure, and these are excluded from the scope of the present disclosure. isn't it. In the examples, "parts" are "parts by mass" and "%" are "% by mass." The blending amounts in the table are parts by mass.
[0149] [Raw material of insulating composition]
[0150] <Acrylic material> ·(a-1) Urethane acrylate oligomer Mw:2100 Contains trifunctional EO chain ·(a-2) Urethane acrylate oligomer Mw:2000 Trifunctional ·(a-3) Urethane acrylate oligomer Mw:1000 5 functionalities ·(a-4) Urethane acrylate oligomer Mw:300 Bifunctional ·(a-5) Urethane acrylate oligomer Mw:14000 Bifunctional ·(a-6) Urethane acrylate oligomer Mw:18000 Bifunctional
[0151] <Photopolymerization initiator> ·Oligo{2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone
[0152] <Polyimide resin> Cyclohexanone (773.5 g) was added to a 4-necked flask equipped with a stirrer, a Dean-Stark device, a reflux condenser, a nitrogen inlet tube, and a thermometer while introducing nitrogen gas. Subsequently, 534.3 g (1.00 mol) of DDA shown in Table 1 as a diamine was added with stirring. Further, 117.58 g (0.524 mol) of TCA and 157.6 g (0.524 mol) of TDA shown in Table 1 as tetracarboxylic dianhydrides were added and stirred at room temperature for 30 minutes. After raising the temperature to 100°C and stirring for 3 hours, the oil bath was removed and the temperature was returned to room temperature to obtain a varnish-like polyimide precursor. Thereafter, using a Dean-Stark apparatus, while removing distilled water from the system, heating was performed at 170° C. for 10 hours to imidize and obtain a polyimide resin solution. Cyclohexane was added to the obtained polyimide resin solution to adjust the nonvolatile content to 50%.
[0153] <Polyamide resin> A polyamide resin solution was obtained in the same manner as for the polyimide resin, except that the monomers listed in Table 1 were used.
[0154] <Evaluation of polyimide resin and polyamide resin> Table 1 shows the results of measuring the weight average molecular weight (Mw), aromatic ring concentration, and functional group concentration depending on the type of terminal functional group of the polyimide resin and polyamide resin obtained in each synthesis example using the measurement method shown below.
[0155] [Weight average molecular weight (Mw)] The weight average molecular weight (Mw) was measured using GPC (gel permeation chromatography) "GPC-101" manufactured by Showa Denko KK. GPC is a liquid chromatography method that separates and quantifies substances dissolved in a solvent (THF: tetrahydrofuran) based on their molecular size differences. The columns used were two "KF-805L" (manufactured by Showa Denko Co., Ltd.: GPC column: 8 mm ID x 300 mm size) connected in series. The measurement was performed under the following conditions: sample concentration of 1% by mass, flow rate of 1.0 mL / min, pressure of 3.8 MPa, and column temperature of 40°C. The weight average molecular weight (Mw) was determined in terms of polystyrene. For data analysis, the calibration curve, molecular weight, and peak area were calculated using the manufacturer's built-in software, and the weight average molecular weight (Mw) was determined.
[0156] [Aromatic ring concentration] The aromatic ring concentration of the polyimide resin and polyamide resin was determined using the above formula (1).
[0157] [Functional group concentration (functional group value)] (Acid value) Approximately 1 g of the sample was accurately weighed into a stoppered Erlenmeyer flask, and 100 mL of cyclohexanone solvent was added to dissolve it. To this, phenolphthalein test solution was added as an indicator and held for 30 seconds. Thereafter, it was titrated with 0.1N alcoholic potassium hydroxide solution until the solution took on a pale pink color. The acid value was determined using formula (2) (unit: mgKOH / g). [Number 2] Acid value (mgKOH / g)=(5.611×a×F) / S (2) S, a, and F in formula (2) represent the following. ·S: Amount of sample collected (g) ·a: Consumption amount of 0.1N alcoholic potassium hydroxide solution (mL) ·F: Potency of 0.1N alcoholic potassium hydroxide solution.
[0158] (Acid anhydride price) Approximately 1 g of the sample was accurately weighed into a stoppered Erlenmeyer flask, and 100 mL of 1,4-dioxane solvent was added to dissolve it. Add 10 mL of a mixed solution of octylamine, 1,4-dioxane, and water (mass mixing ratio is 1.49 / 800 / 80) in an amount greater than the amount of acid anhydride groups in the sample, stir for 15 minutes, and remove the acid anhydride groups. I reacted. Thereafter, excess octylamine was titrated with a mixed solution of 0.02M perchloric acid and 1,4-dioxane. Additionally, 10 mL of a mixed solution of octylamine, 1,4-dioxane, and water (mass mixing ratio: 1.49 / 800 / 80) to which no sample was added was also used as a blank for measurement. Acid anhydride value was calculated using formula (3) (unit: mgKOH / g) [Number 3] Acid anhydride value (mgKOH / g)=0.02×(B-S)×F×56.11 / W (3) B, S, W, and F in formula (3) represent the following. ·B: Blank titer (mL) ·S: Titration amount of sample (mL) ·W: Sample solid amount (g) ·F: 0.02mol / L perchloric acid titer.
[0159]
table 1
[0160] <Manufacture of insulating composition Z> [Insulating composition Z-1] Insulating composition Z-1 was obtained by blending 100 g of urethane acrylate oligomer (a-1) with 5.0 g of a photopolymerization initiator and 100 g of MEK:IPA (isopropanol) = 1:9 as a diluting solvent.
[0161] [Insulating composition Z-2] Insulating composition Z-2 was obtained by blending 100 g of urethane acrylate oligomer (a-2) with 5.0 g of a photopolymerization initiator and 100 g of MEK:IPA (isopropanol) = 1:9 as a diluting solvent.
[0162] [Insulating composition Z-3] Insulating composition Z-3 was obtained by blending 100 g of urethane acrylate oligomer (a-3) with 5.0 g of a photopolymerization initiator and 100 g of MEK:IPA (isopropanol) = 1:9 as a diluting solvent.
[0163] [Insulating composition Z-4] Insulating composition Z-4 was obtained by blending 5.0 g of a photopolymerization initiator and 100 g of MEK:IPA (isopropanol) = 1:9 as a diluting solvent to 100 g of urethane acrylate oligomer (a-4).
[0164] [Insulating composition Z-5] Insulating composition Z-5 was obtained by blending 100 g of urethane acrylate oligomer (a-5) with 5.0 g of a photopolymerization initiator and 100 g of MEK:IPA (isopropanol) = 1:9 as a diluting solvent.
[0165] [Insulating composition Z-6] Insulating composition Z-6 was obtained by blending 5.0 g of a photopolymerization initiator and 100 g of MEK:IPA (isopropanol) = 1:9 as a diluting solvent to 100 g of urethane acrylate oligomer (a-6).
[0166] [Insulating composition Z-7] To 167.8 g of the polyimide resin solution mentioned above, 1.67 g of Tetrad C (epoxy compound (1,3-bis(N,N-diglycidylaminoethyl)cyclohexane, manufactured by Mitsubishi Gas Chemical Co., Ltd.)) as a crosslinking agent and DBU as a catalyst were added. 0.43 g of (1,8-diazabicyclo[5,4,0]-undecene-7) and 30.1 g of toluene as a solvent were mixed and stirred with a mixer to obtain an insulating composition Z-7.
[0167] [Insulating composition Z-8] To 167.8 g of the polyamide resin solution described above, 1.67 g of Tetrad C as a crosslinking agent, 0.43 g of DBU as a catalyst, and 30.1 g of toluene as a solvent were mixed and stirred with a mixer to obtain an insulating composition Z-8.
[0168] [Raw materials for adhesive composition] <Synthesis of acrylic adhesive> 500 g of ethyl acetate was heated in a water bath while nitrogen gas was introduced into a 4-necked flask equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, and a thermometer. Next, 240 g of BA (n-butyl acrylate), 240 g of 2-EHA (2-ethylhexyl acrylate), 20 g of AA (acrylic acid), and 0.5 g of AIBN (azobisisobutyronitrile) as an initiator were added. The added mixture was added dropwise to ethyl acetate and reacted for 8 hours while maintaining reflux. After the reaction, 110 g of ethyl acetate was added to obtain an acrylic adhesive with a nonvolatile content of 45% and a weight average molecular weight (Mw) of 650,000.
[0169] Note that the weight average molecular weight (Mw) was measured under the following conditions. The weight average molecular weight (Mw) was determined by a calibration curve method using polystyrene of known weight average molecular weight as a standard substance. ·Equipment name: Manufactured by Shimadzu Corporation, LC-GPC system “Prominence” ·Column: Manufactured by Tosoh Corporation, TSKgel (registered trademark) α-M, two connected in series ·Mobile phase solvent: Tetrahydrofuran ·Flow rate: 1.0mL / min ·Column temperature: 40℃.
[0170] <Manufacture of adhesive composition N> [Adhesive composition N-1] Adhesive composition N was obtained by blending 0.5 g of an isocyanate curing agent (Duranate TLA-100 manufactured by Asahi Kasei Co., Ltd., NCOwt%: 23.3%) as a crosslinking agent to 100 g of the acrylic adhesive obtained above and stirring and mixing. Got -1.
[0171] [Adhesive composition N-2] Adhesive composition N-2 was obtained by blending 0.5 g of benzoyl oxide and 50 g of MEK with 100 g of silicone adhesive: KR-130 (manufactured by Shin-Etsu Chemical Co., Ltd.) and stirring and mixing.
[0172] <Properties of glass cloth> Table 2 shows the properties of glass cloths G-1 to G-6, which are the raw materials for the glass cloth layers used in the examples.
[0173] [Table 2]
[0174] <Other materials> Release film: SP PET-01-BU, thickness 50μm, silicone release treatment on one side, PET film separator manufactured by Mitsui Chemicals Tocello Co., Ltd.
[0175] [Resin film] ·PI: Aromatic polyimide film (manufactured by DuPont-Toray Co., Ltd., product name: Kapton 100H). ·PEN: Polyethylene naphthalate film (manufactured by Toyobo Co., Ltd., product name: Teonex Q51-25) ·GSF: Resin film with glass fiber filler; After mixing 100 g of insulating composition Z-7 and 10 g of glass fiber filler (milled fiber HP3610, glass filament diameter 10 μm), dry it on a release film to a thickness of 30 μm. The film was prepared by applying the film in a uniform manner, drying it at 150°C, and removing the release film.
[0176] <Manufacture of insulating adhesive tape> [Example 1] Adhesive composition N-1 was applied to the release-treated surface of a 300 mm square release film to a thickness of 30 μm after drying with a doctor blade, and dried in an oven at 100° C. for 5 minutes to obtain an adhesive layer. By laminating and integrating this adhesive layer and glass cloth G-1 with a laminator at a roll pressure of 0.2 MPa, a speed of 100 mm / min, and a temperature of 23°C, the adhesive layer 13 / glass cloth is placed on the release film. A laminate a having layer 11 (adhesive impregnated layer 5 μm, adhesive non-impregnated layer 25 μm, layer thickness 50 μm) was obtained.
[0177] Next, the insulating composition Z-1 was applied with a doctor blade to the surface of the glass cloth layer 11 opposite to the adhesive layer 13 of the laminate a so that the total thickness of the insulating adhesive tape was 60 μm, and After drying with hot air for a minute, the insulating adhesive tape of Example 1 was obtained by curing with a high-pressure mercury lamp at an irradiation intensity of 80 mW / cm2 and an integrated light amount of 500 mJ / cm2. A portion of the insulating adhesive tape ZN-1 was frozen in liquid nitrogen, cut with a razor to obtain a tape cross section, and the thickness of each layer was measured by SEM observation of the cross section at 500x magnification.
[0178] [Examples 2-6, Examples 9-23] Insulating adhesive tapes of Examples 2 to 6 and Examples 9 to 23 were obtained in the same manner as in Example 1, except that the raw materials for the insulating layer were changed to those shown in Tables 3 to 6.
[0179] [Example 7-8] Same as Example 1 except that the raw materials and thickness of each layer were changed to those shown in Tables 3 to 6, the drying temperature of the insulating composition was 150°C, and no ultraviolet irradiation was performed using a mercury lamp. Insulating adhesive tapes of Examples 7 and 8 were obtained by the method described above.
[0180] [Comparative example 1] Laminate a obtained in the manufacturing process of Example 1 was designated as Comparative Example 1.
[0181] [Comparative example 2] An insulating adhesive tape of Comparative Example 2 was obtained in the same manner as in Example 1, except that after creating the adhesive layer 13, the insulating layer was applied directly to the surface of the adhesive layer 13 without bonding the glass cloth layer. .
[0182] [Comparative Examples 3~5] The same procedure as in Example 1 was carried out, except that the resin film PI, PEN, or GSF was attached to the adhesive layer instead of the glass cloth, and then an insulating layer was applied to the resin film surface opposite to the surface in contact with the adhesive layer. By this method, insulating adhesive tapes of Comparative Examples 3 and 4 were obtained.
[0183] The various thicknesses were measured by cross-sectioning by the ion milling method described above, and by SEM observation at 500x magnification, and the average value of the five locations was taken.
[0184] <Evaluation of insulating adhesive tape> Various performance evaluation methods and evaluation criteria for the tapes obtained in each Example and Comparative Example are shown below. Evaluation results based on the following evaluation criteria are shown in Tables 3 to 6.
[0185] [Tracking resistance] As a method for measuring the anti-tracking performance of insulating materials, there is a Proof Tracking Index based on IEC60112, JIS C2134, ASTM D3638, or UL746A. The upper limit of PTI test voltage is specified as 600V. As a method for measuring tracking performance using a high voltage exceeding 600V, there is an Inclined-Plane Tracking (IPT) test based on IEC60587, JIS C2136, or ASTM D2303. The lower limit of IPT test voltage is specified as 1kV (1000V). Since it is not possible to confirm the presence or absence of a reverse trend phenomenon in CTI evaluation conducted from a test starting voltage of 300 volts after the revision of UL746A, in this specification, the test was conducted with the upper limit of the test voltage at 1000 V in accordance with IEC60112, and the following The PTI was measured at the specified voltage. The specified voltages were 300V, 600V, and 1000V. In this specification, when there is a flash, a standard is set separately from the presence of a flash, and it is evaluated as a reverse trend phenomenon. The presence or absence of PTI and reverse trend phenomenon of the insulating adhesive tape was evaluated based on the following evaluation criteria. (Evaluation criteria) S: Test cleared at all specified voltages. A: Test cleared at specified voltage of 600V and 300V, but not achieved at 1000V. B: Test cleared at specified voltages of 600V and 300V, but not achieved at 1000V. There is a flash at the specified 300V (there is a reverse trend phenomenon). C: Test cleared at specified voltage of 600V, but not achieved at 300V and 1000V (with reverse trend phenomenon).
[0186] [Heat-resistant] In accordance with JISC4003:2010, a thermal evaluation test was conducted on the insulating adhesive tape with the release film removed, the heat resistance temperature was measured, and the heat resistance of the insulating adhesive tape was evaluated based on the following evaluation criteria. (Evaluation criteria) S: Heat resistance temperature is 200℃ or higher (Heat resistance class: N, R). A: Heat resistance temperature is 180℃ or higher and lower than 200℃ (heat resistance class: H). B: Heat-resistant temperature is 155°C or higher and lower than 180°C (heat-resistant class: F). C: Heat resistance temperature is less than 155℃ (Heat resistance class: B or lower).
[0187] [Insulation] Three pieces of 25 mm square insulating adhesive tape were prepared, and the dielectric breakdown voltage of each piece was measured once using an AC withstanding voltage tester (7470 manufactured by Keizoku Gijutsu Kenkyusho Co., Ltd.) in accordance with JIS C 2110. The breakdown voltage (kV) was measured in an environment of 23℃ and 50% RH at a frequency of 60Hz and a boost rate of 0.1kV / sec, and the average of the absolute values obtained from a total of 3 measurements for each tape was taken as the breakdown voltage (kV). . The above measurement was performed by attaching the adhesive layer from which the release film was removed to the lower electrode serving as the pedestal of the electrode, and sandwiching one layer so that the upper electrode was in contact with the insulating layer. S is good, A is usable for general purposes, B is usable depending on the usage environment, and C rating is not practical as an insulating adhesive tape. S: 5kV or more A: 4kV or more, less than 5kV B: 3kV or more, less than 4kV C: Less than 3kV
[0188] [Wrapping workability] Cut each insulating adhesive tape into a strip of 2 cm wide and 20 cm long, and wrap the insulating adhesive tape in a direction perpendicular to the length of the tape around a 5 cm long steel circular rod with an outer diameter of 2 mm. To wrap the tape, peel off the release film and start wrapping the exposed adhesive layer around the steel rod, and after wrapping it once, wrap it up to the end of the insulating adhesive tape so that it adheres to the opposite side of the adhesive layer. . The steel rod wrapped with tape was fixed to a jig so that it stood upright, and left to stand for one hour in an environment of 23°C and 50% RH for one day to stabilize the adhesion of the adhesive tape, and four test samples were prepared. Each test sample was exposed to the following four environmental conditions and evaluated based on the following evaluation criteria based on the presence or absence of peeling of the wound tape end. In addition, peeling of the edge was defined as peeling if the adhesive surface peeled off by 1 mm or more from the edge of the tape that was in contact with it before the test. Condition 1: Leave at 100℃ for 1 hour. Condition 2: Leave at 200℃ for 1 hour. Condition 3: Leave in a 100℃ environment for 30 minutes, then place in a -10℃ environment for 30 minutes, repeated 5 times. Condition 4: Leave in a 200℃ environment for 30 minutes, then place in a -10℃ environment for 30 minutes, repeated 5 times. (Evaluation criteria) S: No peeling of the edges was observed under all conditions. best A: There is no peeling under conditions 1, 2, and 3, and peeling is observed under condition 4. Good B: No peeling under conditions 1 and 3, peeling observed under conditions 2 and 4. Can be used for a long time in a general-purpose environment C: No peeling under conditions 1 and 2, peeling observed under conditions 3 and 4. Can be used for short periods in general-purpose environments D: No peeling under condition 1, peeling observed under conditions 2, 3, and 4. Or the shape cannot be maintained. Limited usage environment
[0189] [Table 3]
[0190] [Table 4]
[0191] [Table 5]
[0192] [Table 6]
[0193] In Examples 1 to 23, the reverse trend phenomenon was overcome by combining a specific glass cloth layer, a specific insulating layer, and a specific adhesive layer, and high levels of tracking resistance, insulation, wrapping workability, and heat resistance were achieved. . Furthermore, by staying within the preferred range, further performance improvement can be seen, and while some insulating adhesive tapes have high processability, they also have PTI: 1000V, unparalleled tracking resistance, and high heat resistance. Ta.
[0194] On the other hand, in Comparative Example 1, there is no insulating layer, so the tracking resistance and insulation properties are insufficient, and in Comparative Example 2, there is no glass cloth layer, so the heat resistance and wrapping processability are insufficient, and in Comparative Example 3 and Comparative Examples Comparative Example 5, which uses glass fiber filler instead of glass cloth, has insufficient heat resistance and wrapping processability. Met. [Explanation of symbols]
[0195] 1 Insulating adhesive tape 11 Glass cloth layer 12 Insulating layer 12a Insulating non-impregnated layer 12b Insulating impregnated layer 13 Adhesive layer 13a Adhesive non-impregnated layer 13b Adhesive impregnated layer 14 Thermoplastic resin layer 15 Adhesive layer
Claims
1. An insulating adhesive tape having an insulating layer, an adhesive layer, and a glass cloth layer, The glass cloth layer is located between the insulating layer and the adhesive layer, The glass cloth layer is impregnated with at least one of the insulating layer and the adhesive layer, An insulating adhesive tape, in which the insulating layer is a product cured by active energy rays (however, excluding an insulating adhesive tape having an insulating layer, an adhesive layer, and a glass cloth layer, in which the glass cloth layer is located between the insulating layer and the adhesive layer, the glass cloth layer is impregnated with at least one of the insulating layer or the adhesive layer, the glass cloth layer has a thickness of 10 μm to 50 μm and a weave density of 10 threads / 10 mm to 50 threads / 10 mm, the diameter of glass yarns constituting the glass cloth layer is 100 μm to 500 μm, the insulating layer is a product cured by active energy rays, and the insulating adhesive tape has a thickness of 30 μm to 200 μm).
2. 2. The insulating adhesive tape according to claim 1, wherein the insulating adhesive tape has a thickness of 30 μm to 200 μm.
3. 3. The insulating adhesive tape according to claim 1, wherein the glass cloth layer has a thickness of 10 μm to 50 μm and a weave density of 10 strands / 10 mm to 50 strands / 10 mm.
4. 3. The insulating adhesive tape according to claim 1, wherein the diameter of the glass yarn constituting the glass cloth layer is 100 μm to 500 μm.
5. 3. The insulating adhesive tape according to claim 1, wherein the insulating layer is a layer obtained by curing an acrylic material having a weight average molecular weight of 300 to 15,000.
6. 4. The insulating adhesive tape according to claim 3, wherein the insulating layer is a layer obtained by curing an acrylic material having a weight average molecular weight of 300 to 15,000.
7. 5. The insulating adhesive tape according to claim 4, wherein the insulating layer is a layer obtained by curing an acrylic material having a weight average molecular weight of 300 to 15,000.
8. An insulating adhesive tape further having a thermoplastic resin layer, The insulating adhesive tape according to claim 1 , wherein the thermoplastic resin layer is located between the glass cloth layer and the insulating layer or between the glass cloth layer and the adhesive layer.
9. 9. The insulating adhesive tape according to claim 1, which has a proof tracking index (PTI) of 300 V and 600 V as measured in accordance with a test based on IEC 60112, JIS C2134, or ASTM D3638.
10. 9. The insulating pressure-sensitive adhesive tape according to claim 1, which has a proof tracking index (PTI) of 300 V, 600 V, or 1000 V as measured in accordance with a test based on IEC 60112, JIS C2134, or ASTM D3638.